World Health Organization attribution of burden of foodborne diseases to transmission pathways and foods - Sara M. Pires; Lapo Mughini-Gras; Sandra Hoffmann; Kunihiro Kubota; Shannon E. Majowicz; Martyn D. Kirk; Lucy J. Robertson; Paul R. Torgerson; Lea S. Jakobsen; Antonio Agudo; Li Bai; Tety Rachmawati; et al. (Food Research International, 2026)

Invading brown bullhead catfish (Ameiurus nebulosus) show thermal niche rigidity and benthic niche plasticity: implications for management - Paul J. Blanchfield; Tazi H. Rodrigues; Calum MacNeil; Simon D. Stewart; Finnbar Lee; Brendan J. Hicks; Shane Grayling; Soweeta Fort-D’Ath; Matthew J. Prentice; Cindy Baker; Peter Williams; Robin J.P. Holmes (Biological Invasions, 2026)

An AI-powered smartphone-based solution for rice leaf disease detection and a smart electronic reporting system integrating deep convolutional neural network and the internet of things - Md Shadman Shakib; Nabil H. Bhuiyan; K. Zaman; M.S. Arefin Taibin; Eman Hossen; Md Eyakub Ali; Robin Khisa (Physiological and Molecular Plant Pathology, 2026)

Characterization of the reactions of β-lactoglobulin and potato proteins with chlorogenic acid using a UHPLC-ESI-MS approach - Thore H. Diefenbach; Gijs J.C. Vreeke; David S. Nielsen; Giovanni A. van Kralingen; Robin E.J. Spelbrink; Renske H. Janssen; Wouter J.C. de Bruijn; Jean-Paul Vincken (Food Research International, 2026)

Corrigendum to ‘Associations of residential environmental factors with kidney function in older adults in the Netherlands: A cross-sectional and longitudinal study’ [Environ. Pollut. 397 (2026) 127917] - Kate H. Liang; Marianne C. Verhaar; Natasja M. van Schoor; Gisela G. Slaats; Robin W.M. Vernooij; Erik J. Timmermans (Environmental Pollution, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

The role of estuarine axial convergent fronts in microplastic dispersal - Nia H. Jones; Peter E. Robins; Xiaorong Li; Davey L. Jones; Simon P. Neill (Frontiers in Marine Science, 2026)
Microplastic transport through estuaries represents a critical and poorly understood pathway from catchments and wastewater sources to coastal zones. Microplastics can host microbial communities including pathogenic microorganisms that pose serious public health risks for coastal activities. This study investigated the role of estuarine hydrodynamics on microplastic dispersal in the Conwy estuary, UK, characterised by density-driven secondary flows that can retain microplastics, interspersed with riverine floods that export microplastics seaward. Using the Delft3D hydrodynamic model, parameterised and validated with observational data, we simulated the Axial Convergent Front (ACF) under a range of tidal regimes and river inputs. The ACF formed regularly, lasting between 45 minutes and 2 hours, in the mid and upper-estuary (where salinity was greater than 3 ppt) depending on the saline intrusion that controls the lateral density gradients driving the front. Its strength varied, with cross-channel velocities of between 3.6 (during low river flows) and 4.7 cm s −1 (during high river flows), i.e., 10-20% of the instantaneous longitudinal flow, but tended to not form on channel meanders. Coupling Delft3D to a Lagrangian particle tracking model, we showed that the ACF acts as an additional retention process for microplastics within estuaries, contributing to estuarine pollution sinks. However, high river flow events disrupted ACF formation, and promoted microplastics transport offshore. Limited sorting of microplastics of different densities was simulated because the estuary is shallow and well-mixed with retention times of several days. These results emphasise the necessity of fine-scale three-dimensional modelling, comprehensive microplastic sampling, and improved knowledge of microbial aggregation processes, to accurately represent microplastic dispersal through estuaries. This study advances our understanding of estuarine processes and marine pollution to inform risk assessments and mitigation for microplastic pollution and associated health risks.

Associations of residential environmental factors with kidney function in older adults in the Netherlands: A cross-sectional and longitudinal study - Kate H. Liang; Marianne C. Verhaar; Natasja M. van Schoor; Gisela G. Slaats; Robin W.M. Vernooij; Erik J. Timmermans (Environmental Pollution, 2026)

Integrated Reanalysis of Global Riverine Fish eDNA Datasets Shows Robustness and Congruence of Biodiversity Conclusions - Yan Zhang; Heng Zhang; Hiroshi Akashi; Camille P. Albouy; Kara J. Andres; José Barquín; Jeanine Brantschen; Richard E. Connon; Joseph M. Craine; Deirdre Gleeson; Alejandra Goldenberg‐Vilar; Alexia M. González‐Ferreras; et al. (Molecular Ecology, 2026)
The analysis of environmental DNA (eDNA) has revolutionized biodiversity assessments in aquatic ecosystems, enabling non‐invasive monitoring of fish communities across diverse regions. However, the global comparability of these eDNA datasets remains ambiguous due to heterogeneous sampling protocols and bioinformatic workflows across studies, making it difficult to assess how robust and comparable the biodiversity patterns inferred from these datasets actually are. Here, we conducted a meta‐analysis of 58 riverine fish eDNA metabarcoding studies, covering 1818 sampling sites worldwide, to evaluate the robustness of eDNA‐derived biodiversity patterns. We found that species richness estimates and metrics of community structure derived under a common bioinformatic workflow were overall consistent with those of original analyses, despite the relatively high variability in bioinformatic analyses in the respective original studies. Contrastingly, congruence of species identity varied more extensively across datasets, mostly reflecting different completeness and regional relevance of reference databases. Restricting taxonomic assignment to basin‐specific species pools improved species identification accuracy, while datasets lacking publicly accessible or well‐curated reference data were more prone to mismatches. Year of sampling had a positive effect on taxonomic congruence, such that more recent studies showed increased robustness, also reflecting improved reference database coverage and enhanced species‐level identification over time and overall method congruence in more recent years. Overall, the suitability and potential of eDNA for global biodiversity monitoring is corroborating overall robust biodiversity estimates, irrespective of the bioinformatic approaches. Our study underlines the effectiveness and need for further harmonization of bioinformatic workflows and strengthened region‐specific reference databases for improved taxonomic resolution and comparability across studies.

Metals exposures and telomere length as a marker of DNA damage among electronic waste workers and a reference group - Mabel Sarpong Duah; Ibrahim Issah; Shirley V. Simpson; Serwaa A. Bawua; Duah Dwomoh; Joseph K. H. Bonney; Shinsaku Inomata; Thomas G. Robins; Niladri Basu; Arima Hiroaki; Julius N. Fobil (Environmental Science and Pollution Research, 2026)

Emerging tools to advance neuroethology in butterflies and moths - Francesco Cicconardi; Max S. Farnworth; Robin Grob; Donya N. Shodja; Caroline N. Bacquet; Basil el Jundi; Arnaud Martin; Stephen H. Montgomery (Journal of Comparative Physiology A, 2026)
Butterflies and moths have played historically important roles in developing our understanding of both ecology and evolutionary biology, and neuroethology. In both contexts, the diversity of behavioral strategies and specializations displayed by different Lepidoptera make them informative case studies. However, as in neuroscience more broadly, lepidopteran neuroethology has tended to focus on intricate functional studies within a small number of the most tractable species. In contrast, ecologists and evolutionary biologists have often taken a broader view, using phylogenetic and comparative approaches to extract general patterns of diversification, and to exploit the diversity of butterflies and moths to understand general evolutionary processes. Uniting these approaches and traditions has been restricted, largely due to technical challenges of working with unestablished study systems and a lack of resources beyond basic tools. Now, however, the prospects for broader comparative studies of the neural basis of behavior within a phylogenetic and/or ecological framework are increasingly positive. This is in large part due to the emergence of new molecular sequencing approaches and associated tools. These allow for the survey of cell types, the spatial location of their soma, development of new cell-type markers for targeted analyses, and quantification of the dynamic regulation of gene expression at a tissue or cell specific level. Results of these molecular methods can be combined with technical developments in free flying behavioral experiments in tethered animals that permit neural recordings of natural behavior, and functional genetics tools that can allow for more precise manipulation of these behaviors or the neural structures that support them. Here, we review these new approaches, their potential application, and discuss how we can use them to advance the development of new, integrative systems for studying the neural basis of behavior in butterflies and moths.

The diversity of lepidopteran spatial orientation strategies – neuronal mechanisms and emerging challenges in a changing world - Robin Grob; Max S. Farnworth; Jacqueline Degen; Eric Warrant; Stephen H. Montgomery; Basil el Jundi (Journal of Comparative Physiology A, 2026)
The Lepidoptera, butterflies and moths, display an astonishing diversity of spatial orientation strategies essential for survival, reproduction, and ecological success. These spatial orientation strategies range from basic taxes to light, wind, gravity, and chemical cues, to more advanced strategies such as straight-line dispersal, multigenerational migration across continents, and complex trap-lining foraging involving long-term spatial memory. These orientation behaviours are tightly integrated with the ecological roles of lepidopterans as pollinators, prey, and bioindicators, and are supported by a flexible neuronal network. Of special interest for successful orientation are higher-order integration centres like the mushroom bodies (centres for learning and memory) and the central complex (the centre for spatial orientation and locomotion). These centres support cue integration, compass orientation, memory, and directional decision-making. However, anthropogenic stressors, including habitat fragmentation, light pollution, pesticides, and electromagnetic noise, threaten both the environmental cues and the neural systems facilitating lepidopteran navigation, with potential cascading effects on biodiversity and ecosystem health. By combining insights from behavioural ecology, neurobiology, and conservation, we aim to provide a comprehensive overview of the challenges and adaptations that shape the navigational toolkit of lepidopterans, underlining their significance as animal models for studying spatial orientation in a changing world.

Flame retardant biomarker changes with furniture replacement after flammability standard update - Kathleen R. Attfield; Kimberly Berger; Robin E. Dodson; Deborah H. Bennett; Kathryn M. Rodgers; Rebecca Moran; Tasha Stoiber; Yunzhu Wang; Songmei Gao; Sabrina Crispo Smith; June-Soo Park; Arlene Blum; et al. (Environmental Pollution, 2026)

Forest Ecosystem Multifunctionality: A Systematic Review of Measures and Drivers - Jenickson R. S. Costa; Pedro H. S. Brancalion; François-Xavier Joly; Laura H. P. Simões; Jonathan Bonfanti; Guerric le Maire; Agnès Robin; Joannès Guillemot (Current Forestry Reports, 2026)
Purpose of Review Forest ecosystem multifunctionality, the capacity of forests to simultaneously deliver multiple ecosystem functions and services, is being increasingly affected by pressures stemming from anthropogenic activities and climate change. Here, we conducted a systematic literature review to explore how forest ecosystem multifunctionality was evaluated in the literature, and to identify its main drivers. Recent Findings We found that the number of publications strongly increased in recent years, mostly focused on China and Europe. Abiotic drivers were most frequently examined, ranked in decreasing importance as soil properties, site features, and climate factors. Biodiversity-related drivers were the second most studied, encompassing species composition (i.e., species identity within the forest), species richness of trees, bacteria, and fungi, and stand structural diversity. Soil-related drivers were predominantly used to evaluate belowground multifunctionality, with less consideration given to their potential effects on aboveground multifunctionality. Conversely, the effects of tree and stand attributes have commonly been considered in both above- and belowground ecosystem multifunctionality. Forest ecosystem multifunctionality is often mediated by interactions among drivers, involving both above and below-ground components. Summary Tree species and soil organism diversity (including species richness and functional diversity), stand age and stand structural diversity, emerged as crucial drivers enhancing multifunctionality both above- and belowground. Our results suggest that preserving old-growth forests, promoting long-term restoration, and expanding species-diverse forests is an effective strategy for achieving multifunctional forests. Current understanding is limited by a pronounced geographical bias, limited comparability of studies, and overlooked multifunctionally drivers, especially related to the effects of soil fauna and management practices.

Variation in Social Structure Among Multiple Stocks of Island‐Associated Common Bottlenose Dolphins ( Tursiops truncatus ) in Hawaiian Waters - Enrico Corsi; Robin W. Baird; Annette E. Harnish; Antoinette M. Gorgone; Jens J. Currie; Stephanie H. Stack; Jeremy J. Kiszka (Marine Mammal Science, 2026)
The drivers of animal social structures remain poorly understood, particularly in species such as cetaceans that are wide‐ranging and challenging to study. Understanding the factors shaping sociality can shed light on population ecology, gene flow, and information transmission. Here, we investigated variation in social structure among three independent island‐associated stocks of common bottlenose dolphins ( Tursiops truncatus ) around the main Hawaiian Islands. We generated social networks for each stock using photo‐identification data from 2002 to 2022. We calculated modularity, density, degree centralization, and betweenness centralization to assess network structure. We measured the stocks' available habitat and calculated their population densities. We also quantified association strength with the half‐weight association index (HWI) and compared it within‐ and between‐clusters, and by sex for each stock. HWIs revealed that within‐cluster associations were much stronger than between‐cluster in all stocks. Network modularity and HWI showed the lowest fragmentation into distinct clusters and the strongest associations in the smallest of the three habitats (Kaua‘i‐Ni‘ihau). We found no conclusive evidence of sex differences in HWI. Our findings suggest that denser populations might drive social network fragmentation. Our study highlights the importance of further investigating the drivers of sociality.

The effects of anthropogenic sound on behaviour and physiology in female Port Jackson sharks Heterodontus portusjacksoni (Elasmobranchii) - H. Robins; C.C. Kerr; T.L. Dutka; J.A. Donald; A. Macdonald; S.P. Collin; L. Chapuis (Marine Pollution Bulletin, 2025)

A decision support tool for rubble stabilization on coral reefs - Shu Kiu Leung; Tania M. Kenyon; Laurie J. Raymundo; Helen E. Fox; Nathan Cook; Kailash Cook; Alasdair J. Edwards; Eric E. Fisher; Arnaud J.T. Brival; Freda E. Nicholson; Robin W.L. Philippo; Andrew C.F. Taylor; et al. (Journal of Environmental Management, 2025)

Citizen scientists as butterfly predators: using foraging theory to understand individual recorder behaviour - Mingrui Li; Robin J. Boyd; Chloë Smith; Richard Fox; David Roy; Jonathan Bennie; Richard H. ffrench-Constant (Ecological Modelling, 2025)

Causal risk factors for stroke, delirium, and mortality after elective and urgent open aortic arch surgery for older adults - Mirthe M. van Diepen; Ioan Gabriel Bucur; Ralf W. J. Weijs; Robin H. Heijmen; Tom Claassen; Jurgen A. H. R. Claassen (GeroScience, 2025)

The Martian oxygen green line dayglow: response to solar activity - L. Soret; H. Robin; J.-C. Gérard; L. Gkouvelis; I. Thomas; B. Ristic; Y. Willame; B. Hubert; A.C. Vandaele; J.P. Mason; F. Daerden; M.R. Patel (Icarus, 2025)

History of family member incarceration during childhood and receipt of cancer screenings during adulthood in the United States - Jingxuan Zhao; Kevin H. Miller; Jessica Star; Priti Bandi; K. Robin Yabroff (Cancer Causes & Control, 2025)

Sensory Evaluation of a Powdered Seaweed Seasoning Blend - T. Sutton; H. Park; K. Crowe-White; A. Ferdous; K. Won; A. Robins; A. Ellis (Journal of the Academy of Nutrition and Dietetics, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Spectro-photometry of Phobos simulants II. Effects of porosity and texture - Antonin Wargnier; Olivier Poch; Giovanni Poggiali; Thomas Gautier; Alain Doressoundiram; Pierre Beck; Tomoki Nakamura; Hideaki Miyamoto; Shingo Kameda; Nathalie Ruscassier; Arnaud Buch; Pedro H. Hasselmann; et al. (Icarus, 2025)

Pedotransfer functions and their impact on soil water dynamics simulation and yield prediction: A HERMES model case study - Pablo Rosso; K.-Christian Kersebaum; Jannis Groh; Horst H. Gerke; Kurt Heil; Robin Gebbers (European Journal of Agronomy, 2025)

Improvement of desalination productivity with intermittent impermeable segments - Robin S.M. Chrystie; Talal D. Alshamrani; Isam H. Aljundi (Desalination, 2025)

Coagulation temperature during cellulose regeneration from N-methylmorpholine-N-oxide (NMMO) influences the structure and ease of saccharification of lyocell byproducts - Sebastian España Orozco; Robin Hoheneder; Katharina Steiner; Solène Frécaut; Elisabeth Fitz; Robert H. Bischof (Carbohydrate Polymers, 2025)

Impacts of orthophosphate addition on chloramine decay and biofilm development in a model drinking water distribution system - Mahmoud H. Badawy; Mitchell G. Cooke; Kimia Aghasadeghi; Sigrid Peldszus; Robin M. Slawson; Peter M. Huck (Water Research, 2025)

Optimizing automated photo identification for population assessments - Philip T. Patton; Krishna Pacifici; Robin W. Baird; Erin M. Oleson; Jason B. Allen; Erin Ashe; Aline Athayde; Charla J. Basran; Elsa Cabrera; John Calambokidis; Júlio Cardoso; Emma L. Carroll; et al. (Conservation Biology, 2025)
Several legal acts mandate that management agencies regularly assess biological populations. For species with distinct markings, these assessments can be conducted noninvasively via capture‐recapture and photographic identification (photo‐ID), which involves processing considerable quantities of photographic data. To ease this burden, agencies increasingly rely on automated identification (ID) algorithms. Identification algorithms present agencies with an opportunity—reducing the cost of population assessments—and a challenge—propagating misidentifications into abundance estimates at a large scale. We explored several strategies for generating capture histories with an ID algorithm, evaluating trade‐offs between labor costs and estimation error in a hypothetical population assessment. To that end, we conducted a simulation study informed by 39 photo‐ID datasets representing 24 cetacean species. We fed the results into a custom optimization tool to discern the optimal strategy for each dataset. Our strategies included choosing between truly and partially automated photo‐ID and, in the case of the latter, choosing the number of suggested matches to inspect. True automation was optimal for datasets for which the algorithm identified individuals well. As identification performance declined, the optimization recommended that users inspect more suggested matches from the ID algorithm, particularly for small datasets. False negatives (i.e., individual was resighted but erroneously marked as a first capture) strongly predicted estimation error. A 2% increase in the false negative rate translated to a 5% increase in the relative bias in abundance estimates. Our framework can be used to estimate expected error of the abundance estimate, project labor effort, and find the optimal strategy for a dataset and algorithm. We recommend estimating a strategy's false negative rate before implementing the strategy in a population assessment. Our framework provides organizations with insights into the conservation benefits and consequences of automation as conservation enters a new era of artificial intelligence for population assessments.

Clarifying the role of the resist–accept–direct framework in supporting resource management planning processes - Gregor W. Schuurman; Wylie Carr; Cat Hawkins Hoffman; David J. Lawrence; Brian W. Miller; Erik A. Beever; Jean Brennan; Katherine R. Clifford; Scott Covington; Shelley D. Crausbay; Amanda E. Cravens; John Gross; et al. (Conservation Biology, 2025)

Psilocybin therapy for treatment resistant depression: prediction of clinical outcome by natural language processing - Robert F. Dougherty; Patrick Clarke; Merve Atli; Joanna Kuc; Danielle Schlosser; Boadie W. Dunlop; David J. Hellerstein; Scott T. Aaronson; Sidney Zisook; Allan H. Young; Robin Carhart-Harris; Guy M. Goodwin; et al. (Psychopharmacology, 2025)
Rationale Therapeutic administration of psychedelics has shown significant potential in historical accounts and recent clinical trials in the treatment of depression and other mood disorders. A recent randomized double-blind phase-IIb study demonstrated the safety and efficacy of COMP360, COMPASS Pathways’ proprietary synthetic formulation of psilocybin, in participants with treatment-resistant depression. Objective While the phase-IIb results are promising, the treatment works for a portion of the population and early prediction of outcome is a key objective as it would allow early identification of those likely to require alternative treatment. Methods Transcripts were made from audio recordings of the psychological support session between participant and therapist 1 day post COMP360 administration. A zero-shot machine learning classifier based on the BART large language model was used to compute two-dimensional sentiment (valence and arousal) for the participant and therapist from the transcript. These scores, combined with the Emotional Breakthrough Index (EBI) and treatment arm were used to predict treatment outcome as measured by MADRS scores. (Code and data are available at https://github.com/compasspathways/Sentiment2D .) Results Two multinomial logistic regression models were fit to predict responder status at week 3 and through week 12. Cross-validation of these models resulted in 85% and 88% accuracy and AUC values of 88% and 85%. Conclusions A machine learning algorithm using NLP and EBI accurately predicts long-term patient response, allowing rapid prognostication of personalized response to psilocybin treatment and insight into therapeutic model optimization. Further research is required to understand if language data from earlier stages in the therapeutic process hold similar predictive power.

Relating patatin and lipoxygenase variant profiles to enzymatic activities in potato protein isolates - Thore H. Diefenbach; Gijs J.C. Vreeke; Robin E.J. Spelbrink; Peter A. Wierenga; Jean-Paul Vincken (Food Chemistry, 2025)

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Preoperative physical resilience indicators and their associations with postoperative outcomes - Marjolein Klop; René J. F. Melis; G. M. E. E. Geeske Peeters; Guillaume S. C. Geuzebroek; Robin H. Heijmen; Richard J. A. van Wezel; Jurgen A. H. R. Claassen (GeroScience, 2025)
The health benefit of surgery in older adults may be outweighed by negative effects on cognitive or physical function. Physical resilience is defined as the potential for recovery after a stressor such as surgery. We assessed associations between physical resilience measured by orthostatic blood pressure (BP) and cerebral oxygenation recovery or grip work (sustained hand grip strength; GW) and postoperative outcome in two cohorts of (older) surgical patients. The first cohort (CTC) consisted of patients undergoing complex cardiothoracic surgery. The second cohort (GRR) held geriatric outpatients undergoing various surgical procedures. Outcome measures were length of stay (LoS) and postoperative complications. Negative binomial (LoS) and ordinal (complications) regression models were used to determine associations. 261 patients (113 CTC and 148 GRR) underwent surgery. Median LoS was 10 (CTC) and 5 days (GRR). Postoperative complications occurred in 80% (CTC) and 45% (GRR) of patients. In CTC, 10 mmHg higher systolic BP recovery was associated with a 12% shorter LoS (incidence rate ratio (IRR) 0.88 (95% CI 0.78–0.98)). 10 s longer sustained hand grip was associated with a 5% shorter LoS in GRR (IRR 0.95 (0.90–1.00)), but a 7% longer LoS in CTC (IRR 1.07 (1.03–1.11)). No significant associations were found with postoperative complications. Orthostatic cerebral oxygenation recovery in CTC was not significantly associated with any postoperative outcome. Our results imply that resilience indicators might be associated with LoS after surgery. Future research should seek to replicate our findings and investigate whether adding resilience parameters to preoperative assessment can support postoperative outcome prediction.

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Predicting and assessing the impacts of COVID-19 disruption on marine science and sectors in Australia - Alistair J. Hobday; Vicki M. Walters; Robert L. Stephenson; Shane Baylis; Cindy Bessey; Fabio Boschetti; Catherine Bulman; Stephanie Contardo; Jeffrey M. Dambacher; Jemery Day; Natalie A. Dowling; Piers Dunstan; et al. (Reviews in Fish Biology and Fisheries, 2025)
By March 2020 coronavirus disease 2019 (COVID-19) was anticipated to present a major challenge to the work undertaken by scientists. This pandemic could be considered just one of the shocks that human society has had and will be likely to confront again in the future. As strategic thinking about the future can assist performance and planning of scientific research in the face of change, the pandemic presented an opportunity to evaluate the performance of marine researchers in prediction of future outcomes. In March 2020, two groups of researchers predicted outcomes for the Australian marine research sector, and then evaluated these predictions after 18 months. The self-assessed coping ability of a group experienced in ‘futures studies’ was not higher than the less-experienced group, suggesting that scientists in general may be well placed to cope with shocks. A range of changes to scientific endeavours (e.g., travel, fieldwork) and to marine sectors (e.g., fisheries, biodiversity) were predicted over the first 12–18 months of COVID-19 disruption. The predicted direction of change was generally correct (56%) or neutral (25%) for predictions related to the scientific endeavour, and correct (73%) or mixed (9%) for predictions related to sectors that are the focus of marine research. The success of this foresighting experiment suggests that the collective wisdom of scientists can be used by their organisations to consider the impact of shocks and disruptions and to better prepare for and cope with shocks. Graphical abstract Word cloud analysis of free text responses to questions about expected impact of COVID-19 on the activities associated with marine science

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

Hydraulically linked reservoirs simultaneously fed the 1975–1984 Krafla Fires eruptions: Insights from petrochemistry - Shane M. Rooyakkers; Kate J. Carroll; Alexandra F. Gutai; Ben Winpenny; Enikő Bali; Guðmundur H. Guðfinnsson; John Maclennan; Freysteinn Sigmundsson; Kristján Jónasson; Euan J.F. Mutch; David A. Neave; Jóhann Gunnarsson Robin; et al. (Earth and Planetary Science Letters, 2024)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Effect of surfactants on the permeation rate and selectivity of polyamide composite membranes for organic solvent nanofiltration - Hilal Ahmad; Abdul Waheed; Robin Chrystie; Isam H. Aljundi (Process Safety and Environmental Protection, 2024)

The general external exposome and the development or progression of chronic kidney disease: A systematic review and meta-analyses - Kate H. Liang; Julia M.T. Colombijn; Marianne C. Verhaar; Marc Ghannoum; Erik J. Timmermans; Robin W.M. Vernooij (Environmental Pollution, 2024)

The effect of trees on arbuscular mycorrhizal fungi and grassland root biomass: Case study of two temperate silvopastoral systems - Shevani Murray; Bram Avezaat; Robin Guilmot; Anne A. Hogenboom; Don H. Lareau; Brigitte Wear; Gabriel Y.K. Moinet (Applied Soil Ecology, 2024)

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Transmission of Brucella canis in a canine kennel following introduction of an infected dog - Heather Graham; Marleen van der Most; Andries A. Kampfraath; Vanessa Visser; Annemieke Dinkla; Frank Harders; Robin Ruuls; Alieda van Essen-Zandbergen; Marielle H. van den Esker; Reina van der Heide; Lucien van Keulen; Ad Koets (Veterinary Microbiology, 2024)

Float, fly, then sink: wetland plant seed buoyancy is lost after internal dispersal by waterbirds - María J. Navarro-Ramos; Andy J. Green; Robin de Vries; Casper H. A. van Leeuwen (Hydrobiologia, 2024)
Seed dispersal distance is an important indicator of how well a plant species can cope with environmental changes. Seeds of wetland plants are primarily dispersed by hydrochory (floating on the water surface) or endozoochory (ingestion and egestion by animals). However, both mechanisms can also be combined (diplochory), which increases dispersal distances. In wetlands, seeds often float on the water surface before ingestion and transport by animals, such as waterbirds. Here, we consider what happens next after endozoochory and test whether seeds dispersed inside waterbirds can then continue to disperse by hydrochory. We experimentally assessed the buoyancy capacity of 41 wetland plant species for 14 weeks before and after simulated passage through avian digestive systems. This revealed that (1) seeds of plants previously assigned a hydrochory dispersal syndrome floated longer than those from other syndromes, but with considerable overlap; (2) fully aquatic and shoreline plant species had seeds with stronger buoyancy than terrestrial plants; and (3) digestive processes negatively affected seed buoyancy capacity for all plant species, which included wetland species with a typical hydrochory syndrome. The capacity for hydrochory is more limited after endozoochory than beforehand, with strong implications for the effectiveness of seed dispersal.

Tropical forest succession increases tree taxonomic and functional richness but decreases evenness - Masha T. van der Sande; Lourens Poorter; Géraldine Derroire; Mario Marcos do Espirito Santo; Madelon Lohbeck; Sandra C. Müller; Radika Bhaskar; Michiel van Breugel; Juan Manuel Dupuy‐Rada; Sandra M. Durán; Catarina C. Jakovac; Horacio Paz; et al. (Global Ecology and Biogeography, 2024)
Aim Successional changes in functional diversity provide insights into community assembly by indicating how species are filtered into local communities based on their traits. Here, we assess successional changes in taxonomic and functional richness, evenness and redundancy along gradients of climate, soil pH and forest cover. Location Neotropics. Time period Last 0–100 years. Major taxa studied Trees. Methods We used 22 forest chronosequence studies and 676 plots across the Neotropics to analyse successional changes in Hill's taxonomic and functional diversity of trees, and how these successional changes vary with continental‐scale gradients in precipitation, soil pH and surrounding forest cover. Results Taxonomic and functional richness and functional redundancy increased, while taxonomic and functional evenness decreased over time. Functional richness and evenness changed strongly when not accounting for taxonomic richness, but changed more weakly after statistically accounting for taxonomic richness, indicating that changes in functional diversity are largely driven by taxonomic richness. Nevertheless, the successional increases in functional richness when correcting for taxonomic richness may indicate that environmental heterogeneity and limiting similarity increase during succession. The taxonomically‐independent successional decreases in functional evenness may indicate that stronger filtering and competition select for dominant species with similar trait values, while many rare species and traits are added to the community. Such filtering and competition may also lead to increased functional redundancy. The changes in taxonomically‐independent functional diversity varied with resource availability and were stronger in harsh, resource‐poor environments, but weak in benign, productive environments. Hence, in resource‐poor environments, environmental filtering and facilitation are important, whereas in productive environments, weaker abiotic filtering allows for high initial functional diversity and weak successional changes. Main conclusion We found that taxonomic and functional richness and functional redundancy increased and taxonomic and functional evenness decreased during succession, mainly caused by the increasing number of rare species and traits due to the arrival of new species and due to changing (a)biotic filters.

MXene-enhanced sulfonated TFN nanofiltration membranes for improved desalination performance - Jamilu Usman; Lukka Thuyavan Yogarathinam; Nadeem Baig; Sani I. Abba; Robin Chrystie; Isam H. Aljundi (Desalination, 2024)

Tree demographic strategies largely overlap across succession in Neotropical wet and dry forest communities - Markus E. Schorn; Stephan Kambach; Robin L. Chazdon; Dylan Craven; Caroline E. Farrior; Jorge A. Meave; Rodrigo Muñoz; Michiel van Breugel; Lucy Amissah; Frans Bongers; Bruno Hérault; Catarina C. Jakovac; et al. (Ecology, 2024)
Secondary tropical forests play an increasingly important role in carbon budgets and biodiversity conservation. Understanding successional trajectories is therefore imperative for guiding forest restoration and climate change mitigation efforts. Forest succession is driven by the demographic strategies—combinations of growth, mortality and recruitment rates—of the tree species in the community. However, our understanding of demographic diversity in tropical tree species stems almost exclusively from old‐growth forests. Here, we assembled demographic information from repeated forest inventories along chronosequences in two wet (Costa Rica, Panama) and two dry (Mexico) Neotropical forests to assess whether the ranges of demographic strategies present in a community shift across succession. We calculated demographic rates for >500 tree species while controlling for canopy status to compare demographic diversity (i.e., the ranges of demographic strategies) in early successional (0–30 years), late successional (30–120 years) and old‐growth forests using two‐dimensional hypervolumes of pairs of demographic rates. Ranges of demographic strategies largely overlapped across successional stages, and early successional stages already covered the full spectrum of demographic strategies found in old‐growth forests. An exception was a group of species characterized by exceptionally high mortality rates that was confined to early successional stages in the two wet forests. The range of demographic strategies did not expand with succession. Our results suggest that studies of long‐term forest monitoring plots in old‐growth forests, from which most of our current understanding of demographic strategies of tropical tree species is derived, are surprisingly representative of demographic diversity in general, but do not replace the need for further studies in secondary forests.

Early Aboriginal pottery production and offshore island occupation on Jiigurru (Lizard Island group), Great Barrier Reef, Australia - Sean Ulm; Ian J. McNiven; Glenn R. Summerhayes; Pei-hua Wu; Magdalena M.E. Bunbury; Fiona Petchey; Quan Hua; Robert Skelly; Ariana B.J. Lambrides; Cassandra Rowe; Kelsey M. Lowe; Christian H. Reepmeyer; et al. (Quaternary Science Reviews, 2024)

Lamb meat colour is minimally affected under reduced oxygen concentration in modified atmosphere packaging - Maddison T. Corlett; David W. Pethick; Khama R. Kelman; Robin H. Jacob; Liselotte Pannier; Ihab Habib; Graham E. Gardner (Food Packaging and Shelf Life, 2024)

Triggers affecting crayfish burrowing behaviour - Edwin T. H. M. Peeters; Robin de Vries; Jesper Elzinga; Mercédesz Ludányi; Robbert van Himbeeck; Ivo Roessink (Aquatic Ecology, 2024)
Surface water inhabiting crayfish are well-known for the impact on their surroundings. This impact has been related to loss of biodiversity and deteriorating water quality for invasive crayfish. Crayfish dig burrows for various reasons like lack of natural shelters, avoiding an upcoming drought, or high crayfish density and this may lead to increased sediment transport and accelerated bank instability. All crayfish are considered to have burrowing capability, but not all species have been observed burrowing. Studies comparing this behaviour among different species in standardized ways are scarce. Crayfish burrowing was investigated under standardized laboratory conditions to reveal differences among species and their sex. All studied species occur in the Netherlands and were the native Astacus astacus (Linnaeus, 1758), the Eurasian Pontastacus leptodactylus (Eschscholtz, 1823) and the invasive North American Faxonius virilis (Hagen, 1870), F. limosus (Rafinesque 1817), Pacifastacus leniusculus (Dana, 1852), Procambarus acutus (Girard 1852), and P. clarkii (Girard, 1852). As burrowing triggers were evaluated presence of shelter, increased light intensity, increased water temperature, and increased crayfish density. Results showed species-specific and sometimes sex-specific differences in burrowing behaviour among crayfish. The response to burrowing triggers was also species-specific and no two species reacted identical to all triggers. Absence of shelter was a strong driver to burrow for A. astacus , F. limosus and F. virilis , while increased light intensity triggered burrowing behaviour in P. leptodactylus , P. acutus and P. clarkii and lowered activity of F. limosus . Burrowing behaviour of P. clarkii was mostly influenced by increased water temperature. Significant differences between females and males were observed for P. leptodactylus , P. leniusculus and P. acutus in the shelter, increased density and increased water temperature treatment, respectively. Understanding the triggers that invoke burrowing may help managing populations of these invasive species.

Comment: A reexamination of , bed-scale impact and recovery of a commercially important intertidal seaweed - Robin Hadlock Seeley; Sarah Hardy; Nancy K. Prentiss; Walter H. Adey (Journal of Experimental Marine Biology and Ecology, 2024)

Isotopic and kinetic constraints on methane origins in Icelandic hydrothermal fluids - Andri Stefánsson; Andrea Ricci; Mark Garnett; Jóhann Gunnarsson-Robin; Barbara I. Kleine-Marshall; Samuel W. Scott; Matteo Lelli; Carolina Dantas Cardoso; Raphaël Pik; Chiara Santinelli; Shuhei Ono; Peter H. Barry; et al. (Geochimica et Cosmochimica Acta, 2024)

Luminescence Thermometry Based on the Upconversion Luminescence from the Stark Sublevels of BaY2F8:Yb3+, Tm3+ Phosphor - Ashwini K. Sharma; Govind B. Nair; S. J. Dhoble; Robin E. Kroon; J. J. Terblans; H. C. Swart (Journal of Fluorescence, 2024)
Visible and near-infrared (NIR) upconversion luminescence (UCL) emissions originating from the BaY 2 F 8 : Yb 3+ , Tm 3+ systems were investigated under a laser excitation at 980 nm. The BaY 2 F 8 :20 mol% Yb 3+ , x mol% Tm 3+ and BaY 2 F 8 : y mol% Yb 3+ , 0.5 mol% Tm 3+ phosphors showed prominent UCL at 800 and 810 nm. The optimized doping concentrations of Yb 3+ and Tm 3+ in the BaY 2 F 8 host matrix were evaluated, their spectroscopic properties were determined, and studies on their temperature-dependent behaviour were carried out. The temperature-sensing properties were studied by generating the fluorescence intensity ratio (FIR) of the UCL peaks originating from the thermally-coupled energy levels of the Tm 3+ ions. The Stark sublevels of 1 G 4 level of Tm 3+ ions were utilized to estimate the temperature-sensing abilities of the phosphor. Graphical Abstract

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

SPORA, a new silver phosphate precipitation protocol for oxygen isotope analysis of small, organic-rich bioapatite samples - Gabriele Larocca Conte; Lauren E. Lopes; Aric H. Mine; Robin B. Trayler; Sora L. Kim (Chemical Geology, 2024)

Novel high-yield potato protease inhibitor panels block a wide array of proteases involved in viral infection and crucial tissue damage - Nienke Visser; Laure C. M. Herreman; Jennifer Vandooren; Rafaela Vaz Sousa Pereira; Ghislain Opdenakker; Robin E. J. Spelbrink; Maarten H. Wilbrink; Edwin Bremer; Reinoud Gosens; Martijn C. Nawijn; Heidi H. van der Ende-Metselaar; Jolanda M. Smit; et al. (Journal of Molecular Medicine, 2024)
Viruses critically rely on various proteases to ensure host cell entry and replication. In response to viral infection, the host will induce acute tissue inflammation pulled by granulocytes. Upon hyperactivation, neutrophil granulocytes may cause undue tissue damage through proteolytic degradation of the extracellular matrix. Here, we assess the potential of protease inhibitors (PI) derived from potatoes in inhibiting viral infection and reducing tissue damage. The original full spectrum of potato PI was developed into five fractions by means of chromatography and hydrolysis. Individual fractions showed varying inhibitory efficacy towards a panel of proteases including trypsin, chymotrypsin, ACE2, elastase, and cathepsins B and L. The fractions did not interfere with SARS-CoV-2 infection of Vero E6 cells in vitro. Importantly, two of the fractions fully inhibited elastin-degrading activity of complete primary human neutrophil degranulate. These data warrant further development of potato PI fractions for biomedical purposes, including tissue damage crucial to SARS-CoV-2 pathogenesis. Key messages Protease inhibitor fractions from potato differentially inhibit a series of human proteases involved in viral replication and in tissue damage by overshoot inflammation. Protease inhibition of cell surface receptors such as ACE2 does not prevent virus infection of Vero cells in vitro. Protease inhibitors derived from potato can fully inhibit elastin-degrading primary human neutrophil proteases. Protease inhibitor fractions can be produced at high scale (hundreds of thousands of kilograms, i.e., tons) allowing economically feasible application in lower and higher income countries.

The geographic extent of bird populations affected by renewable‐energy development - Hannah B. Vander Zanden; David M. Nelson; Tara J. Conkling; Taber D. Allison; Jay E. Diffendorfer; Thomas V. Dietsch; Amy L. Fesnock; Scott R. Loss; Patricia A. Ortiz; Robin Paulman; Krysta H. Rogers; Peter M. Sanzenbacher; et al. (Conservation Biology, 2024)
Bird populations are declining globally. Wind and solar energy can reduce emissions of fossil fuels that drive anthropogenic climate change, yet renewable‐energy production represents a potential threat to bird species. Surveys to assess potential effects at renewable‐energy facilities are exclusively local, and the geographic extent encompassed by birds killed at these facilities is largely unknown, which creates challenges for minimizing and mitigating the population‐level and cumulative effects of these fatalities. We performed geospatial analyses of stable hydrogen isotope data obtained from feathers of 871 individuals of 24 bird species found dead at solar‐ and wind‐energy facilities in California (USA). Most species had individuals with a mix of origins, ranging from 23% to 98% nonlocal. Mean minimum distances to areas of likely origin for nonlocal individuals were as close as 97 to >1250 km, and these minimum distances were larger for species found at solar‐energy facilities in deserts than at wind‐energy facilities in grasslands (Cohen's d = 6.5). Fatalities were drawn from an estimated 30–100% of species’ desingated ranges, and this percentage was significantly smaller for species with large ranges found at wind facilities (Pearson's r = −0.67). Temporal patterns in the geographic origin of fatalities suggested that migratory movements and nonmigratory movements, such as dispersal and nomadism, influence exposure to fatality risk for these birds. Our results illustrate the power of using stable isotope data to assess the geographic extent of renewable‐energy fatalities on birds. As the buildout of renewable‐energy facilities continues, accurate assessment of the geographic footprint of wildlife fatalities can be used to inform compensatory mitigation for their population‐level and cumulative effects.

Predicting potential spawning areas of European bass, Dicentrarchus labrax, in the Irish and Celtic seas - H. Lincoln; P.E. Robins; S-B. Wilmes; S. Pérez-Mayol; A. Moore; S. Simpson; A. Goward-Brown; C. Heney; S. Malham; B. Morales-Nin; N. Hold; I.D. McCarthy (Fisheries Research, 2024)

Effect of Structurally Related Compounds on Desupersaturation Kinetics of Indomethacin - Arushi Manchanda; Mustafa Bookwala; Peter L. D. Wildfong; Robin H. Bogner (Pharmaceutical Research, 2023)

MicroRNAs in atrial fibrillation target genes in structural remodelling - Nicoline W. E. van den Berg; Makiri Kawasaki; Fransisca A. Nariswari; Benedetta Fabrizi; Jolien Neefs; Ingeborg van der Made; Robin Wesselink; Wim Jan P. van Boven; Antoine H. G. Driessen; Aldo Jongejan; Joris R. de Groot (Cell and Tissue Research, 2023)
We aim to elucidate how miRNAs regulate the mRNA signature of atrial fibrillation (AF), to gain mechanistic insight and identify candidate targets for future therapies. We present combined miRNA–mRNA sequencing using atrial tissues of patient without AF ( n = 22), with paroxysmal AF ( n = 22) and with persistent AF ( n = 20). mRNA sequencing previously uncovered upregulated epithelial to mesenchymal transition, endothelial cell proliferation and extracellular matrix remodelling involving glycoproteins and proteoglycans in AF. MiRNA co-sequencing discovered miRNAs regulating the mRNA expression changes. Key downregulated miRNAs included miR-135b-5p, miR-138-5p, miR-200a-3p, miR-200b-3p and miR-31-5p and key upregulated miRNAs were miR-144-3p, miR-15b-3p, miR-182-5p miR-18b-5p, miR-4306 and miR-206. MiRNA expression levels were negatively correlated with the expression levels of a multitude of predicted target genes. Downregulated miRNAs associated with increased gene expression are involved in upregulated epithelial and endothelial cell migration and glycosaminoglycan biosynthesis. In vitro inhibition of miR-135b-5p and miR-138-5p validated an effect of miRNAs on multiple predicted targets. Altogether, the discovered miRNAs may be explored in further functional studies as potential targets for anti-fibrotic therapies in AF.

Physiological effects of PFAS exposure in seabird chicks: A multi-species study of thyroid hormone triiodothyronine, body condition and telomere length in South Western France - M. Sebastiano; W. Jouanneau; P. Blévin; F. Angelier; C. Parenteau; M. Pallud; C. Ribout; J. Gernigon; J.C. Lemesle; F. Robin; P. Pardon; H. Budzinski; et al. (Science of The Total Environment, 2023)

Challenges and opportunities in the use of ponds and pondscapes as Nature-based Solutions - M. Cuenca-Cambronero; M. Blicharska; J.-A. Perrin; T. A. Davidson; B. Oertli; M. Lago; M. Beklioglu; M. Meerhoff; M. Arim; J. Teixeira; L. De Meester; J. Biggs; et al. (Hydrobiologia, 2023)
Ponds and “pondscapes” (networks of ponds) are crucial habitats for biodiversity and for delivering multiple benefits to humans, so-called “Nature’s Contribution to People”, such as climate mitigation and adaptation to climate change, creation, and maintenance of habitat for biodiversity, water purification, flood mitigation and cultural benefits (e.g., recreational possibilities). However, ponds are not often considered as Nature-based Solutions to provide all these benefits. In addition, there is insufficient knowledge on how to manage and restore ponds to maximise their role to increase the resilience of ecosystems and society to climate change. To facilitate improved implementation of ponds as Nature-based Solutions for the delivery of a wide range of Nature Contributions to People, it is important to generate and integrate biodiversity, ecosystems, societal, economic and policy knowledge. Hence, there is a need for evidence-based guidance to support the broader use of ponds. Here, we review the role of ponds and pondscapes in delivering Nature’s Contributions to People and provide an overview of the challenges and opportunities for their broader implementation as Nature-based Solutions. Finally, we propose a conceptual framework that can help the implementation of pond Nature-based Solutions, and that outlines future research needs.

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Do we need high temporal resolution modelling of exposure in urban areas? A test case - H. Woodward; A. Schroeder; A. de Nazelle; C.C. Pain; M.E.J. Stettler; H. ApSimon; A. Robins; P.F. Linden (Science of The Total Environment, 2023)

Melissopalynological investigations of seasonal honey samples from the Greater Kruger National Park, Savanna biome of South Africa - Nikiwe Ndlovu; Frank H. Neumann; Michelle D. Henley; Robin M. Cook; Chevonne Reynolds (Palynology, 2023)

Beyond ecology: ecosystem restoration as a process for social-ecological transformation - Anazélia M. Tedesco; Sofía López-Cubillos; Robin Chazdon; Jonathan R. Rhodes; Carla L. Archibald; Katharina-Victoria Pérez-Hämmerle; Pedro H.S. Brancalion; Kerrie A. Wilson; Mariana Oliveira; Diego F. Correa; Liz Ota; Tiffany H. Morrison; et al. (Trends in Ecology & Evolution, 2023)

Portable gamma spectrometry for rapid assessment of soil texture, organic carbon and total nitrogen in agricultural soils - Alex Taylor; Alice Kalnins; Martha Koot; Robin Jackson; Arsenio Toloza; Hami Said Ahmed; Rupert Goddard; William H. Blake (Journal of Soils and Sediments, 2023)

Correction: A well-studied parasitoid fly of field crickets uses multiple alternative hosts in its introduced range - E. Dale Broder; James H. Gallagher; Aaron W. Wikle; Gabrielle T. Welsh; David M. Zonana; Thomas J. Firneno; Robin M. Tinghitella (Evolutionary Ecology, 2023)

A well-studied parasitoid fly of field crickets uses multiple alternative hosts in its introduced range - E Dale Broder; James H Gallagher; Aaron W Wikle; Gabrielle T Welsh; David M Zonana; Thomas J Firneno; Robin M Tinghitella (Evolutionary Ecology, 2023)

Successional shifts in tree demographic strategies in wet and dry Neotropical forests - Nadja Rüger; Markus E. Schorn; Stephan Kambach; Robin L. Chazdon; Caroline E. Farrior; Jorge A. Meave; Rodrigo Muñoz; Michiel van Breugel; Lucy Amissah; Frans Bongers; Dylan Craven; Bruno Hérault; et al. (Global Ecology and Biogeography, 2023)
Aim Tropical forest succession and associated changes in community composition are driven by species demographic rates, but how demographic strategies shift during succession remains unclear. Our goal was to identify generalities in demographic trade‐offs and successional shifts in demographic strategies across Neotropical forests that cover a large rainfall gradient and to test whether the current conceptual model of tropical forest succession applies to wet and dry forests. Location Mexico and Central America. Time period 1985–2018. Major taxa studied Trees. Methods We used repeated forest inventory data from two wet and two dry forests to quantify demographic rates of 781 tree species. For each forest, we explored the main demographic trade‐offs and assigned tree species to five demographic groups by performing a weighted principal components analysis to account for differences in sample size. We aggregated the basal area and abundance across demographic groups to identify successional shifts in demographic strategies over the entire successional gradient from very young ( Results Across all forests, we found two demographic trade‐offs, namely the growth–survival trade‐off and the stature–recruitment trade‐off, enabling the data‐driven assignment of species to five demographic strategies. Fast species dominated early in succession and were then replaced by long‐lived pioneers in three forests. Intermediate and slow species increased in basal area over succession in all forests, but, in contrast to the current conceptual model, long‐lived pioneers continued to dominate until the old‐growth stage in all forests. The basal area of short‐lived breeders was low across all successional stages. Main conclusions The current conceptual model of Neotropical forest succession should be revised to incorporate the dominance of long‐lived pioneers in late‐successional and old‐growth forests. Moreover, the definition of consistent demographic strategies that show clear dominance shifts across succession substantially improves the mechanistic understanding and predictability of Neotropical forest succession.

Emerging themes and future directions in watershed resilience research - Fernando Miralles-Wilhelm; John H. Matthews; Nathan Karres; Robin Abell; James Dalton; Shi-Teng Kang; Junguo Liu; Romain Maendly; Nathanial Matthews; Robert McDonald; Raúl Muñoz-Castillo; Boris F. Ochoa-Tocachi; et al. (Water Security, 2023)

Deep magma degassing and volatile fluxes through volcanic hydrothermal systems: Insights from the Askja and Kverkfjöll volcanoes, Iceland - Eemu Ranta; Sæmundur A. Halldórsson; Peter H. Barry; Shuhei Ono; Jóhann Gunnarsson Robin; Barbara I. Kleine; Andrea Ricci; Jens Fiebig; Árný E. Sveinbjörnsdóttir; Andri Stefánsson (Journal of Volcanology and Geothermal Research, 2023)

Cross-continental differences in Black-tailed Godwit breeding densities are best explained by arthropod abundance in the chick-hatching period - Miguel Silva-Monteiro; Hannes Pehlak; Sami Timonen; Jorma Pessa; Esko Pasanen; Mo Verhoeven; A. H. Jelle Loonstra; Theunis Piersma; Frederic Robin; Michał Korniluk; Melissa Onwezen; Morten Bongers; et al. (Journal of Ornithology, 2023)

Polystyrene nanoplastics enhance the toxicological effects of DDE in zebrafish (Danio rerio) larvae - Shubham Varshney; Adnan H. Gora; Viswanath Kiron; Prabhugouda Siriyappagouder; Dalia Dahle; Tanja Kögel; Robin Ørnsrud; Pål A. Olsvik (Science of The Total Environment, 2023)

Bungarus fasciatus venom from eastern and north-east India: venom variation and immune cross-reactivity with Indian polyvalent antivenoms - Amit Talukdar; Anita Malhotra; H. T. Lalremsanga; Vishal Santra; Robin Doley (Journal of Proteins and Proteomics, 2023)

Corrigendum to “Priorities to inform research on marine plastic pollution in Southeast Asia” [Sci. Total Environ. volume 841 (2022) Article 156704] - Lucy C.M. Omeyer; Emily M. Duncan; Kornrawee Aiemsomboon; Nicola Beaumont; Sujaree Bureekul; Bin Cao; Luis R. Carrasco; Suchana Chavanich; James R. Clark; Muhammad R. Cordova; Fay Couceiro; Simon M. Cragg; et al. (Science of The Total Environment, 2023)

Getting the most out of maths: How to coordinate mathematical modelling research to support a pandemic, lessons learnt from three initiatives that were part of the COVID-19 response in the UK - Ciara E. Dangerfield; I. David Abrahams; Chris Budd; Matt Butchers; Michael E. Cates; Alan R. Champneys; Christine S.M. Currie; Jessica Enright; Julia R. Gog; Alain Goriely; T. Déirdre Hollingsworth; Rebecca B. Hoyle; et al. (Journal of Theoretical Biology, 2023)

How long do bracken (Pteridium aquilinum (L.) Kuhn) control treatments maintain effectiveness? - Ilgın Akpınar; Josu G. Alday; Emma Cox; H.A. McAllister; Michael G. Le Duc; Robin J. Pakeman; Rob H. Marrs (Ecological Engineering, 2023)

Population estimates of photo-identified individuals using a modified POPAN model reveal that Raja Ampat’s reef manta rays are thriving - Edy Setyawan; Ben C. Stevenson; Mark V. Erdmann; Abdi W. Hasan; Abraham B. Sianipar; Imanuel Mofu; Mochamad I. H. Putra; Muhamad Izuan; Orgenes Ambafen; Rachel M. Fewster; Robin Aldridge-Sutton; Ronald Mambrasar; et al. (Frontiers in Marine Science, 2022)
The 6.7-million-hectare Raja Ampat archipelago is home to Indonesia’s largest reef manta ray ( Mobula alfredi ) population and a representative network of nine marine protected areas (MPAs). However, the population dynamics of M. alfredi in the region are still largely unknown. Using our photo-identification database, we fitted modified POPAN mark-recapture models with transience and per capita recruitment parameters to estimate key demographic characteristics of M. alfredi from two of Raja Ampat’s largest MPAs: Dampier Strait and South East (SE) Misool. A total of 1,041 unique individuals were photo-identified over an 11-year period (2009–2019) from Dampier Strait (n = 515) and SE Misool (n = 536). In our models, apparent survival probabilities and per capita recruitment rates were strongly linked with El Niño–Southern Oscillation (ENSO) events. Our models also estimated high apparent survival probabilities and significant increases in (sub)population sizes in both MPAs over a decade. In Dampier Strait, the estimated population size increased significantly (p = 0.018) from 226 (95% CI: 161, 283) to 317 (280, 355) individuals. Likewise, the estimated population size in SE Misool increased significantly (p = 0.008) from 210 (137, 308) to 511 (393, 618) individuals. Regardless of variation in the percentage change in population size between years throughout the study, the estimated overall population change shows a compound growth of 3.9% (0.7, 8.6) per annum in Dampier Strait and 10.7% (4.3, 16.1) per annum in SE Misool. Despite the global decline in oceanic sharks and rays due to fishing pressure in the last five decades, our study demonstrates the positive impact of a suite of long-term conservation efforts, coupled with the influence of ENSO events, on increasing M. alfredi abundance in Raja Ampat MPAs. Our study also underscores the importance of long-term monitoring to evaluate the effectiveness of conservation management measures on manta ray populations. Our modification of the standard POPAN model by incorporating per capita recruitment and transience parameters represents an important advance in mark-recapture modelling that should prove useful when examining other manta ray populations and other highly migratory species that are likely to have a substantial percentage of transient individuals.

Corrigendum: Associations between cyanobacteria and indices of secondary production in the western basin of Lake Erie - James H. Larson; Mary Anne Evans; Robert J. Kennedy; Sean W. Bailey; Keith A. Loftin; Zachary R. Laughrey; Robin A. Femmer; Jeff S. Schaeffer; William B. Richardson; Timothy T. Wynne; J. C. Nelson; Joseph W. Duris (Limnology and Oceanography, 2022)
In the last year, we became aware that data used in our above‐referenced manuscript from 2018 published in Limnology and Oceanography contained significant errors. In the 2018 manuscript, we found that indices of secondary production were negatively correlated to indices of cyanobacterial abundance and toxicity. Unfortunately, one of our indices of cyanobacterial abundance (biovolume) and our measurement of toxicity (microcystin concentration) were inaccurate in the data we used in the 2018 manuscript. Upon discovering these errors, we immediately began correcting the repositories where these data were available. Having corrected those data repositories, we are now reporting on the re‐analysis of the data using the methods previously described in the 2018 manuscript. Although the relationships are slightly different, our interpretation is that the conclusions of the 2018 manuscript are still valid using the corrected data. The data errors we experienced were traced to a spreadsheet that was used to share data among the research team, which had errors caused by mistakes in copy‐pasting formulas instead of data and ‘inadvertent’ edits that were saved by the spreadsheet's auto‐save function. We apologize to the scientific community for these errors.

Δ9-THC reduces reward-related brain activity in healthy adults - Conor H. Murray; James E. Glazer; Royce Lee; Robin Nusslock; Harriet de Wit (Psychopharmacology, 2022)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Predicting landscape‐scale biodiversity recovery by natural tropical forest regrowth - Pablo V. Prieto; Jacob J. Bukoski; Felipe S. M. Barros; Hawthorne L. Beyer; Alvaro Iribarrem; Pedro H. S. Brancalion; Robin L. Chazdon; David B. Lindenmayer; Bernardo B. N. Strassburg; Manuel R. Guariguata; Renato Crouzeilles (Conservation Biology, 2022)
Natural forest regrowth is a cost‐effective, nature‐based solution for biodiversity recovery, yet different socioenvironmental factors can lead to variable outcomes. A critical knowledge gap in forest restoration planning is how to predict where natural forest regrowth is likely to lead to high levels of biodiversity recovery, which is an indicator of conservation value and the potential provisioning of diverse ecosystem services. We sought to predict and map landscape‐scale recovery of species richness and total abundance of vertebrates, invertebrates, and plants in tropical and subtropical second‐growth forests to inform spatial restoration planning. First, we conducted a global meta‐analysis to quantify the extent to which recovery of species richness and total abundance in second‐growth forests deviated from biodiversity values in reference old‐growth forests in the same landscape. Second, we employed a machine‐learning algorithm and a comprehensive set of socioenvironmental factors to spatially predict landscape‐scale deviation and map it. Models explained on average 34% of observed variance in recovery (range 9–51%). Landscape‐scale biodiversity recovery in second‐growth forests was spatially predicted based on socioenvironmental landscape factors (human demography, land use and cover, anthropogenic and natural disturbance, ecosystem productivity, and topography and soil chemistry); was significantly higher for species richness than for total abundance for vertebrates (median range‐adjusted predicted deviation 0.09 vs. 0.34) and invertebrates (0.2 vs. 0.35) but not for plants (which showed a similar recovery for both metrics [0.24 vs. 0.25]); and was positively correlated for total abundance of plant and vertebrate species (Pearson r = 0.45, p = 0.001). Our approach can help identify tropical and subtropical forest landscapes with high potential for biodiversity recovery through natural forest regrowth.

Acute effects of Δ9-tetrahydrocannabinol and cannabidiol on auditory mismatch negativity - Lisa-Marie Greenwood; Samantha J. Broyd; Hendrika H. van Hell; Juanita Todd; Alison Jones; Robin M. Murray; Rodney J. Croft; Patricia T. Michie; Nadia Solowij (Psychopharmacology, 2022)

Applying Mendelian randomization to appraise causality in relationships between nutrition and cancer - Kaitlin H. Wade; James Yarmolinsky; Edward Giovannucci; Sarah J. Lewis; Iona Y. Millwood; Marcus R. Munafò; Fleur Meddens; Kimberley Burrows; Joshua A. Bell; Neil M. Davies; Daniela Mariosa; Noora Kanerva; et al. (Cancer Causes & Control, 2022)
Dietary factors are assumed to play an important role in cancer risk, apparent in consensus recommendations for cancer prevention that promote nutritional changes. However, the evidence in this field has been generated predominantly through observational studies, which may result in biased effect estimates because of confounding, exposure misclassification, and reverse causality. With major geographical differences and rapid changes in cancer incidence over time, it is crucial to establish which of the observational associations reflect causality and to identify novel risk factors as these may be modified to prevent the onset of cancer and reduce its progression. Mendelian randomization (MR) uses the special properties of germline genetic variation to strengthen causal inference regarding potentially modifiable exposures and disease risk. MR can be implemented through instrumental variable (IV) analysis and, when robustly performed, is generally less prone to confounding, reverse causation and measurement error than conventional observational methods and has different sources of bias (discussed in detail below). It is increasingly used to facilitate causal inference in epidemiology and provides an opportunity to explore the effects of nutritional exposures on cancer incidence and progression in a cost-effective and timely manner. Here, we introduce the concept of MR and discuss its current application in understanding the impact of nutritional factors (e.g., any measure of diet and nutritional intake, circulating biomarkers, patterns, preference or behaviour) on cancer aetiology and, thus, opportunities for MR to contribute to the development of nutritional recommendations and policies for cancer prevention. We provide applied examples of MR studies examining the role of nutritional factors in cancer to illustrate how this method can be used to help prioritise or deprioritise the evaluation of specific nutritional factors as intervention targets in randomised controlled trials. We describe possible biases when using MR, and methodological developments aimed at investigating and potentially overcoming these biases when present. Lastly, we consider the use of MR in identifying causally relevant nutritional risk factors for various cancers in different regions across the world, given notable geographical differences in some cancers. We also discuss how MR results could be translated into further research and policy. We conclude that findings from MR studies, which corroborate those from other well-conducted studies with different and orthogonal biases, are poised to substantially improve our understanding of nutritional influences on cancer. For such corroboration, there is a requirement for an interdisciplinary and collaborative approach to investigate risk factors for cancer incidence and progression.

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

The natural history of OTOF-related auditory neuropathy spectrum disorders: a multicenter study - Ryan K. Thorpe; Hela Azaiez; Peina Wu; Qiuju Wang; Lei Xu; Pu Dai; Tao Yang; G. Bradley Schaefer; B. Robert Peters; Kenny H. Chan; Krista S. Schatz; Joann Bodurtha; et al. (Human Genetics, 2022)

Establishment of a microsatellite genetic baseline for North American Atlantic sturgeon (Acipenser o. oxyrhinchus) and range-wide analysis of population genetics - Shannon L. White; David C. Kazyak; Tanya L. Darden; Daniel J. Farrae; Barbara A. Lubinski; Robin L. Johnson; Michael S. Eackles; Matthew T. Balazik; Harold M. Brundage; Adam G. Fox; Dewayne A. Fox; Christian H. Hager; et al. (Conservation Genetics, 2021)

The Dutch National TissueArchive Portal enables efficient, consistent, and transparent procurement of diagnostic tissue samples for scientific use - Robin Verjans; Annette H. Bruggink; Robby Kibbelaar; Jos Bart; Aletta Debernardi; Tieneke B. M. Schaaij-Visser; Stefan M. Willems; Folkert J. Van Kemenade (Cell and Tissue Banking, 2021)
Biobanks play a crucial role in enabling biomedical research by facilitating scientific use of valuable human biomaterials. The PALGA foundation—a nationwide network and registry of histo- and cytopathology in the Netherlands—was established to promote the provision of data within and between pathology departments, and to make the resulting knowledge available for healthcare. Apart from the pathology data, we aimed to utilize PALGA’s nationwide network to find and access the rich wealth of Formalin-Fixed Paraffin-Embedded (FFPE) tissue samples for scientific use. We implemented the Dutch National TissueArchive Portal (DNTP) to utilize PALGA’s nationwide network for requesting FFPE tissue samples. The DNTP consists of (1) a centrally organized internet portal to improve the assessing, processing, harmonization, and monitoring of the procurement process, while (2) dedicated HUB-employees provide practical support at peripheral pathology departments. Since incorporation of the DNTP, both the number of filed requests for FFPE tissue samples and the amount of HUB-mediated support increased 55 and 29% respectively. In line, the sample procurement duration time decreased significantly (− 47%). These findings indicate that implementation of the DNTP improved the frequency, efficiency, and transparency of FFPE tissue sample procurement for research in the Netherlands. To conclude, the need for biological resources is growing persistently to enable precision medicine. Here, we access PALGA’s national, pathology network by implementation of the DNTP to allow for efficient, consistent, and transparent exchange of FFPE tissue samples for research across the Netherlands.

Global drivers of avian haemosporidian infections vary across zoogeographical regions - Alan Fecchio; Nicholas J. Clark; Jeffrey A. Bell; Heather R. Skeen; Holly L. Lutz; Gabriel M. De La Torre; Jefferson A. Vaughan; Vasyl V. Tkach; Fabio Schunck; Francisco C. Ferreira; Érika M. Braga; Camile Lugarini; et al. (Global Ecology and Biogeography, 2021)
Aim Macroecological analyses provide valuable insights into factors that influence how parasites are distributed across space and among hosts. Amid large uncertainties that arise when generalizing from local and regional findings, hierarchical approaches applied to global datasets are required to determine whether drivers of parasite infection patterns vary across scales. We assessed global patterns of haemosporidian infections across a broad diversity of avian host clades and zoogeographical realms to depict hotspots of prevalence and to identify possible underlying drivers. Location Global. Time period 1994–2019. Major taxa studied Avian haemosporidian parasites (genera Plasmodium , Haemoproteus , Leucocytozoon and Parahaemoproteus ). Methods We amalgamated infection data from 53,669 individual birds representing 2,445 species world‐wide. Spatio‐phylogenetic hierarchical Bayesian models were built to disentangle potential landscape, climatic and biotic drivers of infection probability while accounting for spatial context and avian host phylogenetic relationships. Results Idiosyncratic responses of the three most common haemosporidian genera to climate, habitat, host relatedness and host ecological traits indicated marked variation in host infection rates from local to global scales. Notably, host ecological drivers, such as migration distance for Plasmodium and Parahaemoproteus , exhibited predominantly varying or even opposite effects on infection rates across regions, whereas climatic effects on infection rates were more consistent across realms. Moreover, infections in some low‐prevalence realms were disproportionately concentrated in a few local hotspots, suggesting that regional‐scale variation in habitat and microclimate might influence transmission, in addition to global drivers. Main conclusions Our hierarchical global analysis supports regional‐scale findings showing the synergistic effects of landscape, climate and host ecological traits on parasite transmission for a cosmopolitan and diverse group of avian parasites. Our results underscore the need to account for such interactions, in addition to possible variation in drivers across regions, to produce the robust inference required to predict changes in infection risk under future scenarios.

Response to “Withering the coloniality of the forest transition?” - Thomas K. Rudel; Patrick Meyfroidt; Robin Chazdon; Frans Bongers; Sean Sloan; H. Ricardo Grau; Tracy Van Holt (Ambio, 2021)

Synchronous peritoneal metastases from lung cancer: incidence, associated factors, treatment and survival: a Dutch population-based study - Robin J. Lurvink; Anouk Rijken; Checca Bakkers; Mieke J. Aarts; Peter W. A. Kunst; Ben E. van de Borne; Felice N. van Erning; Ignace H. J. T. de Hingh (Clinical & Experimental Metastasis, 2021)
Peritoneal metastases (PM) from lung cancer are rare and it is unknown how they affect the prognosis of patients with lung cancer. This population-based study aimed to assess the incidence, associated factors, treatment and prognosis of PM from lung cancer. Data from the Netherlands Cancer Registry were used. All patients diagnosed with lung cancer between 2008 and 2018 were included. Logistic regression analysis was performed to identify factors associated with the presence of PM. Cox regression analysis was performed to identify factors associated with the overall survival (OS) of patients with PM. Between 2008 and 2018, 129,651 patients were diagnosed with lung cancer, of whom 2533 (2.0%) patients were diagnosed with PM. The European Standardized Rate of PM increased significantly from 0.6 in 2008 to 1.4 in 2018 (p < 0.001). Age between 50 and 74 years, T3–4 tumour stage, N2–3 nodal stage, tumour morphology of a small cell lung cancer or adenocarcinoma, and the presence of systemic metastases were associated with the presence of PM. The median OS of patients with PM was 2.5 months. Older age, male sex, T3–4 tumour stage, N2–3 nodal stage, not receiving systemic treatment, and the presence of systemic metastases were associated with a worse OS. Synchronous PM were diagnosed in 2.0% of patients with lung cancer and resulted in a very poor survival.

Relationship Between Metabolic Fitness and Performance in Police Occupational Tasks - Elisa F. D. Canetti; J. Jay Dawes; Phoebe H. Drysdale; Robert Lockie; Charlie Kornhauser; Ryan Holmes; Ben Schram; Robin M. Orr (Journal of Science in Sport and Exercise, 2021)
Purpose To determine the relationship between metabolic fitness test scores and performance in police occupational tasks. Methods Retrospective data from 106 law enforcement officers who completed two metabolic fitness assessments [anaerobic: a 20-m (10-m and 20-m splits) sprint, aerobic: 20 m Multi-Stage Fitness Test (20 m-MSFT)] and three routine occupational tasks [1.22 m Fence jump (FJ), 8.5 m Victim Drag (VD with 102.3 kg) and “Get-up” (GU)] were collected. A Person’s correlation coefficient and a standard multiple regression were used to assess the relationship between and predictive ability of, respectively, the fitness tests scores and performance on occupational tasks. Results There was a significant positive correlation between the 10-m sprint scores and FJ ( r = 0.524, P < 0.001), VD ( r = 0.528, P < 0.001) and GU ( r = 0.486, P < 0.001). Similarly, the 20-m sprint scores were significantly and moderately correlated with FJ ( r = 0.573, P < 0.001), VD ( r = 0.603, P < 0.001) and GU ( r = 0.533, P < 0.001). These anaerobic tests’ scores predicted approximately 40% of the performance in the occupational tasks analysed. The MSFT fitness assessment had a small, albeit significant negative correlation with the three tasks: FJ ( r = − 0.360, P < 0.001), VD ( r = − 0.266, P = 0.012) and GU ( r = − 0.375, P < 0.001). Conclusion High levels of metabolic fitness correlated with faster performance in police officer occupational tasks, particularly ones of an anaerobic nature (i.e. the maximal sprint tests). In addition to typical aerobic fitness conditioning, anaerobic fitness conditioning could be vital for optimal performance in physically demanding tasks required of police officer.

Remote Predictions of Mahi-Mahi (Coryphaena hippurus) Spawning in the Open Ocean Using Summarized Accelerometry Data - Lela S. Schlenker; Robin Faillettaz; John D. Stieglitz; Chi Hin Lam; Ronald H. Hoenig; Georgina K. Cox; Rachael M. Heuer; Christina Pasparakis; Daniel D. Benetti; Claire B. Paris; Martin Grosell (Frontiers in Marine Science, 2021)
Identifying complex behaviors such as spawning and fine-scale activity is extremely challenging in highly migratory fish species and is becoming increasingly critical knowledge for fisheries management in a warming ocean. Habitat use and migratory pathways have been extensively studied in marine animals using pop-up satellite archival tags (PSATs), but high-frequency data collected on the reproductive and swimming behaviors of marine fishes has been limited by the inability to remotely transmit these large datasets. Here, we present the first application of remotely transmitted acceleration data to predict spawning and discover drivers of high activity in a wild and highly migratory pelagic fish, the mahi-mahi ( Coryphaena hippurus ). Spawning events were predicted to occur at nighttime, at a depth distinct from non-spawning periods, primarily between 27.5 and 30°C, and chiefly at the new moon phase in the lunar cycle. Moreover, throughout their large-scale migrations, mahi-mahi exhibited behavioral thermoregulation to remain largely between 27 and 28°C and reduced their relative activity at higher temperatures. These results show that unveiling fine-scale activity patterns are necessary to grasp the ecology of highly mobile species. Further, our study demonstrates that critical, and new, ecological information can be extracted from PSATs, greatly expanding their potential to study the reproductive behavior and population connectivity in highly migratory fishes.

Correction to: Evaluation of Predictors of Protein Relative Stability Obtained by \Solid-State Hydrogen/Deuterium Exchange Monitored by FTIR - Rui Fang; Wasfy Obeidat; Michael J. Pikal; Robin H. Bogner (Pharmaceutical Research, 2021)

TGF-β1 increases permeability of ciliated airway epithelia via redistribution of claudin 3 from tight junction into cell nuclei - Carolin Schilpp; Robin Lochbaum; Peter Braubach; Danny Jonigk; Manfred Frick; Paul Dietl; Oliver H. Wittekindt (Pflügers Archiv - European Journal of Physiology, 2021)
TGF-β1 is a major mediator of airway tissue remodelling during atopic asthma and affects tight junctions (TJs) of airway epithelia. However, its impact on TJs of ciliated epithelia is sparsely investigated. Herein we elaborated effects of TGF-β1 on TJs of primary human bronchial epithelial cells. We demonstrate that TGF-β1 activates TGF-β1 receptors TGFBR1 and TGFBR2 resulting in ALK5-mediated phosphorylation of SMAD2. We observed that TGFBR1 and -R2 localize specifically on motile cilia. TGF-β1 activated accumulation of phosphorylated SMAD2 (pSMAD2-C) at centrioles of motile cilia and at cell nuclei. This triggered an increase in paracellular permeability via cellular redistribution of claudin 3 (CLDN3) from TJs into cell nuclei followed by disruption of epithelial integrity and formation of epithelial lesions. Only ciliated cells express TGF-β1 receptors; however, nuclear accumulations of pSMAD2-C and CLDN3 redistribution were observed with similar time course in ciliated and non-ciliated cells. In summary, we demonstrate a role of motile cilia in TGF-β1 sensing and showed that TGF-β1 disturbs TJ permeability of conductive airway epithelia by redistributing CLDN3 from TJs into cell nuclei. We conclude that the observed effects contribute to loss of epithelial integrity during atopic asthma.

Muted responses to chronic experimental nitrogen deposition on the Colorado Plateau - Michala L. Phillips; Daniel E. Winkler; Robin H. Reibold; Brooke B. Osborne; Sasha C. Reed (Oecologia, 2021)

Buffering effects of soil seed banks on plant community composition in response to land use and climate - Jan Plue; Hans Van Calster; Inger Auestad; Sofía Basto; Renée M. Bekker; Hans Henrik Bruun; Richard Chevalier; Guillaume Decocq; Ulf Grandin; Martin Hermy; Hans Jacquemyn; Anna Jakobsson; et al. (Global Ecology and Biogeography, 2021)
Aim Climate and land use are key determinants of biodiversity, with past and ongoing changes posing serious threats to global ecosystems. Unlike most other organism groups, plant species can possess dormant life‐history stages such as soil seed banks, which may help plant communities to resist or at least postpone the detrimental impact of global changes. This study investigates the potential for soil seed banks to achieve this. Location Europe. Time period 1978–2014. Major taxa studied Flowering plants. Methods Using a space‐for‐time/warming approach, we study plant species richness and composition in the herb layer and the soil seed bank in 2,796 community plots from 54 datasets in managed grasslands, forests and intermediate, successional habitats across a climate gradient. Results Soil seed banks held more species than the herb layer, being compositionally similar across habitats. Species richness was lower in forests and successional habitats compared to grasslands, with annual temperature range more important than mean annual temperature for determining richness. Climate and land‐use effects were generally less pronounced when plant community richness included seed bank species richness, while there was no clear effect of land use and climate on compositional similarity between the seed bank and the herb layer. Main conclusions High seed bank diversity and compositional similarity between the herb layer and seed bank plant communities may provide a potentially important functional buffer against the impact of ongoing environmental changes on plant communities. This capacity could, however, be threatened by climate warming. Dormant life‐history stages can therefore be important sources of diversity in changing environments, potentially underpinning already observed time‐lags in plant community responses to global change. However, as soil seed banks themselves appear, albeit less, vulnerable to the same changes, their potential to buffer change can only be temporary, and major community shifts may still be expected.

Genetic analysis of maydis leaf blight resistance in subtropical maize (Zea mays L.) germplasm - B. Jeevan; Robin Gogoi; Devender Sharma; C. Manjunatha; H. Rajashekara; Dama Ram; K. K. Mishra; M. G. Mallikarjuna (Journal of Genetics, 2020)

Evaluation of Predictors of Protein Relative Stability Obtained by Solid-State Hydrogen/Deuterium Exchange Monitored by FTIR - Rui Fang; Wasfy Obeidat; Michael J. Pikal; Robin H. Bogner (Pharmaceutical Research, 2020)

Identification of crucial stepping stone habitats for biodiversity conservation in northeastern Madagascar using remote sensing and comparative predictive modeling - Dominik Schüßler; Jasmin Mantilla-Contreras; Robin Stadtmann; Jonah H. Ratsimbazafy; Ute Radespiel (Biodiversity and Conservation, 2020)
Madagascar is a global biodiversity hotspot of conservation concern. The decline of natural forest habitats due to shifting cultivation has been one of the major land use changes during the last decades. We analyzed satellite images between 1990 and 2018 from northeastern Madagascar to evaluate the contribution of nine variables (e.g., topographic, demographic, forest protection) to explain past forest loss, predict future deforestation probabilities to define important areas that require further conservation attention. Forest cover declined by 21% since 1990 and the once continuous rain forest belt of the region is disrupted twice, in the center and at the southern limit of the study region. Status of forest protection and proximity to the forest edge were identified as most important predictors, but all variables contributed to explaining the observed pattern of deforestation. At least 20% of the 3136 villages in the area were established since 1990 at the expense of previously forested areas. This housing sprawl was mainly driven by accessibility, decreasing landscape connectivity. To conserve the unique biodiversity of the region, the expansion of protected forests and active reforestation measures are urgently needed. Sustainable land use planning and forest management integrating the needs of local land users and conservation priorities should be promoted. We see the highest potential for external stakeholders (e.g., national NGOs) to implement targeted interventions embedded in community-based approaches. Our land cover maps and predictive modeling highlight crucial areas that could act as stepping stone habitats for dispersing or retreating species and therefore important locations to intensify conservation measures.

Age-related murine hippocampal CA1 laminae oxidative stress measured in vivo by QUEnch-assiSTed (QUEST) MRI: impact of isoflurane anesthesia - Bruce A. Berkowitz; Robert H. Podolsky; Karen Lins Childers; Alexander Gow; Brandy L. Schneider; Scott C. Lloyd; Kelly E. Bosse; Alana C. Conti; Robin Roberts; Ali M. Berri; Emma Graffice; Kenan Sinan; et al. (GeroScience, 2020)
Age-related impairments in spatial learning and memory often precede non-familial neurodegenerative disease. Ex vivo studies suggest that physiologic age-related oxidative stress in hippocampus area CA1 may contribute to prodromal spatial disorientation and to morbidity. Yet, conventional blood or cerebrospinal fluid assays appear insufficient for early detection or management of oxidative stress within CA1 sub-regions in vivo. Here, we address this biomarker problem using a non-invasive MRI index of CA1 laminae oxidative stress based on reduction in R1 (= 1/T1) after anti-oxidant administration. An R1 reduction reflects quenching of continuous and excessive production of endogenous paramagnetic free radicals. Careful motion-correction image acquisition, and avoiding repeated exposure to isoflurane, facilitates detection of hippocampus CA1 laminae oxidative stress with QUEnch-assiSTed (QUEST) MRI. Intriguingly, age- and isoflurane-related oxidative stress is localized to the stratum lacunosum of the CA1 region. Our data raise the possibility of using QUEST MRI and FDA-approved anti-oxidants to remediate spatial disorientation and later neurodegeneration with age in animals and humans.

Application of multiple‐population viability analysis to evaluate species recovery alternatives - Helen M. Neville; Douglas R. Leasure; Daniel C. Dauwalter; Jason B. Dunham; Robin Bjork; Kurt A. Fesenmyer; Nathan D. Chelgren; Mary M. Peacock; Charles H. Luce; Daniel J. Isaak; Lee Ann Carranza; Jon Sjoberg; et al. (Conservation Biology, 2020)
Population viability analysis (PVA) is a powerful conservation tool, but it remains impractical for many species, particularly species with multiple, broadly distributed populations for which collecting suitable data can be challenging. A recently developed method of multiple‐population viability analysis (MPVA), however, addresses many limitations of traditional PVA. We built on previous development of MPVA for Lahontan cutthroat trout (LCT) ( Oncorhynchus clarkii henshawi ), a species listed under the U.S. Endangered Species Act, that is distributed broadly across habitat fragments in the Great Basin (U.S.A.). We simulated potential management scenarios and assessed their effects on population sizes and extinction risks in 211 streams, where LCT exist or may be reintroduced. Conservation populations (those managed for recovery) tended to have lower extinction risks than nonconservation populations (mean = 19.8% vs. 52.7%), but not always. Active management or reprioritization may be warranted in some cases. Eliminating non‐native trout had a strong positive effect on overall carrying capacities for LCT populations but often did not translate into lower extinction risks unless simulations also reduced associated stochasticity (to the mean for populations without non‐native trout). Sixty fish or 5–10 fish/km was the minimum reintroduction number and density, respectively, that provided near‐maximum reintroduction success. This modeling framework provided crucial insights and empirical justification for conservation planning and specific adaptive management actions for this threatened species. More broadly, MPVA is applicable to a wide range of species exhibiting geographic rarity and limited availability of abundance data and greatly extends the potential use of empirical PVA for conservation assessment and planning.

Age, geological setting, and paragenesis of heavy rare earth element mineralization of the Tanami region, Western Australia - Teimoor Nazari-Dehkordi; Carl Spandler; Nicholas H. S. Oliver; Robin Wilson (Mineralium Deposita, 2020)

Bioextractive Removal of Nitrogen by Oysters in Great Bay Piscataqua River Estuary, New Hampshire, USA - Suzanne B. Bricker; Raymond E. Grizzle; Philip Trowbridge; Julie M. Rose; Joao G. Ferreira; Katharine Wellman; Changbo Zhu; Eve Galimany; Gary H. Wikfors; Camille Saurel; Robin Landeck Miller; James Wands; et al. (Estuaries and Coasts, 2020)
Eutrophication is a challenge to coastal waters around the globe. In many places, nutrient reductions from land-based sources have not been sufficient to achieve desired water quality improvements. Bivalve shellfish have shown promise as an in-water strategy to complement land-based nutrient management. A local-scale production model was used to estimate oyster ( Crassostrea virginica ) harvest and bioextraction of nitrogen (N) in Great Bay Piscataqua River Estuary (GBP), New Hampshire, USA, because a system-scale ecological model was not available. Farm-scale N removal results (0.072 metric tons acre −1 year −1 ) were up-scaled to provide a system-wide removal estimate for current (0.61 metric tons year −1 ), and potential removal (2.35 metric tons year −1 ) at maximum possible expansion of licensed aquaculture areas. Restored reef N removal was included to provide a more complete picture. Nitrogen removal through reef sequestration was ~ 3 times that of aquaculture. Estimated reef-associated denitrification, based on previously reported rates, removed 0.19 metric tons N year −1 . When all oyster processes (aquaculture and reefs) were included, N removal was 0.33% and 0.54% of incoming N for current and expanded acres, respectively. An avoided cost approach, with wastewater treatment as the alternative management measure, was used to estimate the value of the N removed. The maximum economic value for aquaculture-based removal was $105,000 and $405,000 for current and expanded oyster areas, respectively. Combined aquaculture and reef restoration is suggested to maximize N reduction capacity while limiting use conflicts. Comparison of removal based on per oyster N content suggests much lower removal rates than model results, but model harvest estimates are similar to reported harvest. Though results are specific to GBP, the approach is transferable to estuaries that support bivalve aquaculture but do not have complex system-scale hydrodynamic or ecological models.

Whither the forest transition? Climate change, policy responses, and redistributed forests in the twenty-first century - Thomas K. Rudel; Patrick Meyfroidt; Robin Chazdon; Frans Bongers; Sean Sloan; H. Ricardo Grau; Tracy Van Holt; Laura Schneider (Ambio, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Porous Media Characterization Using Minkowski Functionals: Theories, Applications and Future Directions - Ryan T. Armstrong; James E. McClure; Vanessa Robins; Zhishang Liu; Christoph H. Arns; Steffen Schlüter; Steffen Berg (Transport in Porous Media, 2019)

Killer whale genomes reveal a complex history of recurrent admixture and vicariance - Andrew D. Foote; Michael D. Martin; Marie Louis; George Pacheco; Kelly M. Robertson; Mikkel‐Holger S. Sinding; Ana R. Amaral; Robin W. Baird; Charles Scott Baker; Lisa Ballance; Jay Barlow; Andrew Brownlow; et al. (Molecular Ecology, 2019)
Reconstruction of the demographic and evolutionary history of populations assuming a consensus tree‐like relationship can mask more complex scenarios, which are prevalent in nature. An emerging genomic toolset, which has been most comprehensively harnessed in the reconstruction of human evolutionary history, enables molecular ecologists to elucidate complex population histories. Killer whales have limited extrinsic barriers to dispersal and have radiated globally, and are therefore a good candidate model for the application of such tools. Here, we analyse a global data set of killer whale genomes in a rare attempt to elucidate global population structure in a nonhuman species. We identify a pattern of genetic homogenisation at lower latitudes and the greatest differentiation at high latitudes, even between currently sympatric lineages. The processes underlying the major axis of structure include high drift at the edge of species' range, likely associated with founder effects and allelic surfing during postglacial range expansion. Divergence between Antarctic and non‐Antarctic lineages is further driven by ancestry segments with up to four‐fold older coalescence time than the genome‐wide average; relicts of a previous vicariance during an earlier glacial cycle. Our study further underpins that episodic gene flow is ubiquitous in natural populations, and can occur across great distances and after substantial periods of isolation between populations. Thus, understanding the evolutionary history of a species requires comprehensive geographic sampling and genome‐wide data to sample the variation in ancestry within individuals.

Molecular analysis and new records of the invasive polychaete Boccardia proboscidea (Annelida: Spionidae) - VASILY I. RADASHEVSKY; VICTORIA V. PANKOVA; VASILY V. MALYAR; TATYANA V. NERETINA; ROBIN S. WILSON; TIM M. WORSFOLD; MARÍA E. DIEZ; LESLIE H. HARRIS; STÉPHANE HOURDEZ; CÉLINE LABRUNE; CÉLINE HOUBIN; BRITTA KIND; et al. (Mediterranean Marine Science, 2019)
The spionid polychaete Boccardia proboscidea Hartman, 1940 is a tube-dweller and shell/stone-borer widely occurring in temperate waters across the world and considered invasive in many areas. It was originally described from California, USA, and later reported from Pacific Canada, the Asian Pacific, Australia, New Zealand, Argentina, South Africa, and northern Europe. The Bayesian inference analysis of sequence data of three gene fragments (836 bp in total) of the mitochondrial 16S rDNA, nuclear 28S rDNA, and Histone 3 has shown that individuals from the Pacific coasts of Canada and the USA, Argentina, Australia, South Africa, the United Kingdom, and Mediterranean France were genetically very similar (maximal average p-distance value, 0.49%, was between 16S rDNA sequences). We consider these individuals to be conspecific and report the earliest records of B. proboscidea from the UK and a possible first Mediterranean record in the Gulf of Lion. The high 16S haplotype diversity of B. proboscidea detected in the north-eastern Pacific suggests a native distribution for the species in the northern Pacific and subsequent introductions through human activities to other parts of the world. The histories of these introductions are reviewed and the hypotheses about times and places of introductions are updated.

Molecular analysis and new records of the invasive polychaete Boccardia proboscidea (Annelida: Spionidae) - VASILY I. RADASHEVSKY; VICTORIA V. PANKOVA; VASILY V. MALYAR; TATYANA V. NERETINA; ROBIN S. WILSON; TIM M. WORSFOLD; MARÍA E. DIEZ; LESLIE H. HARRIS; STÉPHANE HOURDEZ; CÉLINE LABRUNE; CÉLINE HOUBIN; BRITTA KIND; et al. (Mediterranean Marine Science, 2019)
The spionid polychaete Boccardia proboscidea Hartman, 1940 is a tube-dweller and shell/stone-borer widely occurring in temperate waters across the world and considered invasive in many areas. It was originally described from California, USA, and later reported from Pacific Canada, the Asian Pacific, Australia, New Zealand, Argentina, South Africa, and northern Europe. The Bayesian inference analysis of sequence data of three gene fragments (836 bp in total) of the mitochondrial 16S rDNA, nuclear 28S rDNA, and Histone 3 has shown that individuals from the Pacific coasts of Canada and the USA, Argentina, Australia, South Africa, the United Kingdom, and Mediterranean France were genetically very similar (maximal average p-distance value, 0.49%, was between 16S rDNA sequences). We consider these individuals to be conspecific and report the earliest records of B. proboscidea from the UK and a possible first Mediterranean record in the Gulf of Lion. The high 16S haplotype diversity of B. proboscidea detected in the north-eastern Pacific suggests a native distribution for the species in the northern Pacific and subsequent introductions through human activities to other parts of the world. The histories of these introductions are reviewed and the hypotheses about times and places of introductions are updated.

A gene for resistance to the Varroa mite (Acari) in honey bee ( Apis mellifera ) pupae - Benjamin H. Conlon; Adriana Aurori; Alexandru‐Ioan Giurgiu; John Kefuss; Daniel S. Dezmirean; Robin F. A. Moritz; Jarkko Routtu (Molecular Ecology, 2019)
Social insect colonies possess a range of defences which protect them against highly virulent parasites and colony collapse. The host–parasite interaction between honey bees ( Apis mellifera ) and the mite Varroa destructor is unusual, as honey bee colonies are relatively poorly defended against this parasite. The interaction has existed since the mid‐20th Century, when Varroa switched host to parasitize A. mellifera . The combination of a virulent parasite and relatively naïve host means that, without acaricides, honey bee colonies typically die within 3 years of Varroa infestation. A consequence of acaricide use has been a reduced selective pressure for the evolution of Varroa resistance in honey bee colonies. However, in the past 20 years, several natural‐selection‐based breeding programmes have resulted in the evolution of Varroa ‐resistant populations. In these populations, the inhibition of Varroa' s reproduction is a common trait. Using a high‐density genome‐wide association analysis in a Varroa ‐resistant honey bee population, we identify an ecdysone ‐induced gene significantly linked to resistance. Ecdysone both initiates metamorphosis in insects and reproduction in Varroa . Previously, using a less dense genetic map and a quantitative trait loci analysis, we have identified Ecdysone ‐related genes at resistance loci in an independently evolved resistant population. Varroa cannot biosynthesize ecdysone but can acquire it from its diet. Using qPCR, we are able to link the expression of ecdysone ‐linked resistance genes to Varroa 's meals and reproduction. If Varroa co‐opts pupal compounds to initiate and time its own reproduction, mutations in the host's ecdysone pathway may represent a key selection tool for honey bee resistance and breeding.

Climate‐driven convergent evolution of plumage colour in a cosmopolitan bird - Andrea Romano; Robin Séchaud; Alexandre H. Hirzel; Alexandre Roulin (Global Ecology and Biogeography, 2019)
Aim The investigation of phenotypic diversity across geographical gradients is pivotal to understanding the evolution and adaptive functions of alternative phenotypes. The aim of the present study was to investigate whether the polymorphism in ventral plumage colouration observed in the cosmopolitan common barn owl group is determined by climatic factors, such as temperature and rainfall, consistent with Gloger’s and Bogert’s biogeographical rules. Location World. Time period 1809–2017. Major taxa studied Tyto alba species complex. Methods We analysed the variation in heritable melanin‐based plumage colour according to annual temperature and rainfall in 9,110 individuals of the cosmopolitan barn owl, with three distinct evolutionary lineages representing its entire distribution range: the Afro‐European Tyto alba , occurring between Scandinavia and South Africa, the American Tyto furcata , found from southern Canada to Patagonia, and the Australasian Tyto javanica , living between the Himalayan Plateau and Tasmania. Results Although the geographical distribution of colour morphs is heterogeneous among the lineages, in all of them plumage colour becomes darker with increasing annual rainfall, indicating a convergent selection of darker morphs in humid habitats possibly to improve camouflage against the dark environment and/or to repel water more efficiently. Moreover, in T. alba and T. furcata , melanization increases at decreasing temperature, suggesting its possible role in thermoregulation. Discussion These findings provide convincing evidence of repeated evolution of similar body colouration patterns at a worldwide scale compatible with the main biogeographical rules, while emphasizing the possible role of melanin‐based traits in animal adaptation to climate change.

Microplastic ingestion ubiquitous in marine turtles - Emily M. Duncan; Annette C. Broderick; Wayne J. Fuller; Tamara S. Galloway; Matthew H. Godfrey; Mark Hamann; Colin J. Limpus; Penelope K. Lindeque; Andrew G. Mayes; Lucy C. M. Omeyer; David Santillo; Robin T. E. Snape; et al. (Global Change Biology, 2019)
Despite concerns regarding the environmental impacts of microplastics, knowledge of the incidence and levels of synthetic particles in large marine vertebrates is lacking. Here, we utilize an optimized enzymatic digestion methodology, previously developed for zooplankton, to explore whether synthetic particles could be isolated from marine turtle ingesta. We report the presence of synthetic particles in every turtle subjected to investigation ( n = 102) which included individuals from all seven species of marine turtle, sampled from three ocean basins (Atlantic [ATL]: n = 30, four species; Mediterranean (MED): n = 56, two species; Pacific (PAC): n = 16, five species). Most particles ( n = 811) were fibres (ATL: 77.1% MED: 85.3% PAC: 64.8%) with blue and black being the dominant colours. In lesser quantities were fragments (ATL: 22.9%: MED: 14.7% PAC: 20.2%) and microbeads (4.8%; PAC only; to our knowledge the first isolation of microbeads from marine megavertebrates). Fourier transform infrared spectroscopy (FT‐IR) of a subsample of particles ( n = 169) showed a range of synthetic materials such as elastomers (MED: 61.2%; PAC: 3.4%), thermoplastics (ATL: 36.8%: MED: 20.7% PAC: 27.7%) and synthetic regenerated cellulosic fibres (SRCF; ATL: 63.2%: MED: 5.8% PAC: 68.9%). Synthetic particles being isolated from species occupying different trophic levels suggest the possibility of multiple ingestion pathways. These include exposure from polluted seawater and sediments and/or additional trophic transfer from contaminated prey/forage items. We assess the likelihood that microplastic ingestion presents a significant conservation problem at current levels compared to other anthropogenic threats.

Genetic analysis and satellite tracking reveal origin of the green turtles in San Diego Bay - Peter H. Dutton; Robin A. LeRoux; Erin L. LaCasella; Jeffrey A. Seminoff; Tomoharu Eguchi; Donna L. Dutton (Marine Biology, 2019)

Hierarchical multi‐population viability analysis - Douglas R. Leasure; Seth J. Wenger; Nathan D. Chelgren; Helen M. Neville; Daniel C. Dauwalter; Robin Bjork; Kurt A. Fesenmyer; Jason B. Dunham; Mary M. Peacock; Charlie H. Luce; Abby C. Lute; Daniel J. Isaak (Ecology, 2019)
Population viability analysis ( PVA ) uses concepts from theoretical ecology to provide a powerful tool for quantitative estimates of population dynamics and extinction risks. However, conventional statistical PVA requires long‐term data from every population of interest, whereas many species of concern exist in multiple isolated populations that are only monitored occasionally. We present a hierarchical multi‐population viability analysis model that increases inference power from sparse data by sharing information among populations to assess extinction risks while accounting for incomplete detection and sampling biases with explicit observation and sampling sub‐models. We present a case study in which we customized this model for historical population monitoring data (1985–2015) from federally threatened Lahontan cutthroat trout populations in the Great Basin, USA . Data were counts of fish captured during backpack electrofishing surveys from locations associated with 155 isolated populations. Some surveys (25%) included multi‐pass removal sampling, which provided valuable information about capture efficiency. GIS and remote sensing were used to estimate August stream temperatures, peak flows, and riparian vegetation condition in each population each year. Field data were used to derive an annual index of nonnative trout densities. Results indicated that population growth rates were higher in colder streams and that nonnative trout reduced carrying capacities of native trout. Extinction risks increased with more environmental stochasticity and were also related to population extent, water temperatures, and nonnative densities. We developed a graphical user interface to interact with the fitted model results and to simulate future habitat scenarios and management actions to assess their influence on extinction risks in each population. Hierarchical multi‐population viability analysis bridges the gap between site‐level field observations and population‐level processes, making effective use of existing datasets to support management decisions with robust estimates of population dynamics, extinction risks, and uncertainties.

Pan‐tropical prediction of forest structure from the largest trees - Jean‐François Bastin; Ervan Rutishauser; James R. Kellner; Sassan Saatchi; Raphael Pélissier; Bruno Hérault; Ferry Slik; Jan Bogaert; Charles De Cannière; Andrew R. Marshall; John Poulsen; Patricia Alvarez‐Loyayza; et al. (Global Ecology and Biogeography, 2018)
Aim Large tropical trees form the interface between ground and airborne observations, offering a unique opportunity to capture forest properties remotely and to investigate their variations on broad scales. However, despite rapid development of metrics to characterize the forest canopy from remotely sensed data, a gap remains between aerial and field inventories. To close this gap, we propose a new pan‐tropical model to predict plot‐level forest structure properties and biomass from only the largest trees. Location Pan‐tropical. Time period Early 21st century. Major taxa studied Woody plants. Methods Using a dataset of 867 plots distributed among 118 sites across the tropics, we tested the prediction of the quadratic mean diameter, basal area, Lorey's height, community wood density and aboveground biomass (AGB) from the i th largest trees. Results Measuring the largest trees in tropical forests enables unbiased predictions of plot‐ and site‐level forest structure. The 20 largest trees per hectare predicted quadratic mean diameter, basal area, Lorey's height, community wood density and AGB with 12, 16, 4, 4 and 17.7% of relative error, respectively. Most of the remaining error in biomass prediction is driven by differences in the proportion of total biomass held in medium‐sized trees (50–70 cm diameter at breast height), which shows some continental dependency, with American tropical forests presenting the highest proportion of total biomass in these intermediate‐diameter classes relative to other continents. Main conclusions Our approach provides new information on tropical forest structure and can be used to generate accurate field estimates of tropical forest carbon stocks to support the calibration and validation of current and forthcoming space missions. It will reduce the cost of field inventories and contribute to scientific understanding of tropical forest ecosystems and response to climate change.

Rare loss of function variants in candidate genes and risk of colorectal cancer - Elisabeth A. Rosenthal; Brian H. Shirts; Laura M. Amendola; Martha Horike-Pyne; Peggy D. Robertson; Fuki M. Hisama; Robin L. Bennett; Michael O. Dorschner; Deborah A. Nickerson; Ian B. Stanaway; Rami Nassir; Kathy T. Vickers; et al. (Human Genetics, 2018)

Species-specific nitrogenase activity in lichen-dominated biological soil crusts from the Colorado Plateau, USA - Terry J. Torres-Cruz; Armin J. Howell; Robin H. Reibold; Theresa A. McHugh; Mackenzie A. Eickhoff; Sasha C. Reed (Plant and Soil, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

A model for assessing iceberg hazard - Grant R. Bigg; T. E. Cropper; Clare K. O’Neill; Alex K. Arnold; A. H. Fleming; R. Marsh; V. Ivchenko; Nicolas Fournier; Mike Osborne; Robin Stephens (Natural Hazards, 2018)

Influence of predation risk on the sheltering behaviour of the coral-dwelling damselfish, Pomacentrus moluccensis - Robin P. M. Gauff; Sonia Bejarano; Hawis H. Madduppa; Beginer Subhan; Elyne M. A. Dugény; Yuda A. Perdana; Sebastian C. A. Ferse (Environmental Biology of Fishes, 2018)

The LEGATO cross-disciplinary integrated ecosystem service research framework: an example of integrating research results from the analysis of global change impacts and the social, cultural and economic system dynamics of irrigated rice production - Joachim H. Spangenberg; Alexis L. Beaurepaire; Erwin Bergmeier; Benjamin Burkhard; Ho Van Chien; Le Quoc Cuong; Christoph Görg; Volker Grescho; Le Huu Hai; Kong Luen Heong; Finbarr G. Horgan; Stefan Hotes; et al. (Paddy and Water Environment, 2018)

Associations between cyanobacteria and indices of secondary production in the western basin of Lake Erie - James H. Larson; Mary Anne Evans; Robert J. Kennedy; Sean W. Bailey; Keith A. Loftin; Zachary R. Laughrey; Robin A. Femmer; Jeff S. Schaeffer; William B. Richardson; Timothy T. Wynne; J. C. Nelson; Joseph W. Duris (Limnology and Oceanography, 2018)
Large lakes provide a variety of ecological services to surrounding cities and communities. Many of these services are supported by ecological processes that are threatened by the increasing prevalence of cyanobacterial blooms which occur as aquatic ecosystems experience cultural eutrophication. Over the past 10 yr, Lake Erie experienced cyanobacterial blooms of increasing severity and frequency, which have resulted in impaired drinking water for the surrounding communities. Cyanobacterial blooms may impact ecological processes that support other services, but many of these impacts have not been documented. Secondary production (production of primary consumers) is an important process that supports economically important higher trophic levels. Cyanobacterial blooms may influence secondary production because cyanobacteria are a poor‐quality food resource and cyanotoxins may be harmful to consumers. Over 3 yr at 34 sites across the western basin of Lake Erie, we measured three indices of secondary production that focus on the dominant bivalve taxa: (1) growth of a native unionid mussel, (2) the size of young‐of‐year dreissenid mussels, and (3) the mass of colonizing animals on a Hester‐Dendy sampler. Associations between these indices and cyanobacterial data were estimated to assess whether cyanobacteria are associated with variation in secondary production in the western basin of Lake Erie. The results suggest cyanobacterial abundance alone is only weakly associated with secondary production, but that cyanotoxins have a larger effect on secondary production. Given recurring late‐summer cyanobacterial blooms, this impact on secondary production has the potential to undermine Lake Erie's ability to sustain important ecosystem services.

Adapting clonally propagated crops to climatic changes: a global approach for taro (Colocasia esculenta (L.) Schott) - V. Lebot; V. Tuia; A. Ivancic; G. V. H. Jackson; F. Saborio; G. Reyes; S. Rodriguez; G. Robin; R. Traoré; L. Aboagye; J. Onyeka; W. van Rensburg; et al. (Genetic Resources and Crop Evolution, 2018)

Phosphorus and nitrogen starvation reveal life‐cycle specific responses in the metabolome of Emiliania huxleyi (Haptophyta) - Robin Wördenweber; Sebastian D. Rokitta; Elena Heidenreich; Katrin Corona; Frank Kirschhöfer; Kirsten Fahl; Jessica L. Klocke; Tilman Kottke; Gerald Brenner‐Weiß; Björn Rost; Jan H. Mussgnug; Olaf Kruse (Limnology and Oceanography, 2018)
The coccolithophore Emiliania huxleyi is a microalga with biogeochemical and biotechnological relevance, due to its high abundance in the ocean and its ability to form intricate calcium carbonate structures. Depletion of macronutrients in oceanic waters is very common and will likely enhance with advancing climate change. We present the first comprehensive metabolome study analyzing the effect of phosphorus (P) and nitrogen (N) starvation on the diploid and haploid life‐cycle stage, applying various metabolome analysis methods to gain new insights in intracellular mechanisms to cope with nutrient starvation. P‐starvation led to an accumulation of many generic and especially N‐rich metabolites, including lipids, osmolytes, and pigments. This suggests that P‐starvation primarily arrests cell‐cycling due to lacking P for nucleic acid synthesis, but that enzymatic functionality is widely preserved. Also, the de‐epoxidation ratio of the xanthophyll cycle was upregulated in the diploid stage under P‐starvation, indicating increased nonphotochemical quenching, a response typically observed under high light stress. In contrast, N‐starvation resulted in a decrease of most central metabolites, also P‐containing ones, especially in the diploid stage, indicating that most enzymatic functionality ceased. The two investigated nutrient starvation conditions caused significantly different responses, contrary to previous assumptions derived from transcriptomic studies. Data highlight that instantaneous biochemical flux is a more dominant driver of the metabolome than the transcriptomically rearranged pathway patterns. Due to the fundamental nature of the observed responses it may be speculated that microalgae with similar nutrient requirements can cope better with P‐starvation than with N‐starvation.

Banded Leaf and Sheath Blight of Maize: Historical Perspectives, Current Status and Future Directions - K. S. Hooda; M. K. Khokhar; H. Parmar; Robin Gogoi; Deeksha Joshi; S. S. Sharma; O. P. Yadav (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2017)

Familial social structure and socially driven genetic differentiation in Hawaiian short‐finned pilot whales - Amy M. Van Cise; Karen. K. Martien; Sabre D. Mahaffy; Robin W. Baird; Daniel L. Webster; James H. Fowler; Erin M. Oleson; Phillip A. Morin (Molecular Ecology, 2017)
Social structure can have a significant impact on divergence and evolution within species, especially in the marine environment, which has few environmental boundaries to dispersal. On the other hand, genetic structure can affect social structure in many species, through an individual preference towards associating with relatives. One social species, the short‐finned pilot whale ( Globicephala macrorhynchus ), has been shown to live in stable social groups for periods of at least a decade. Using mitochondrial control sequences from 242 individuals and single nucleotide polymorphisms from 106 individuals, we examine population structure among geographic and social groups of short‐finned pilot whales in the Hawaiian Islands, and test for links between social and genetic structure. Our results show that there are at least two geographic populations in the Hawaiian Islands: a Main Hawaiian Islands ( MHI ) population and a Northwestern Hawaiian Islands/Pelagic population ( F ST and Φ ST p .001), as well as an eastern MHI community and a western MHI community ( F ST p = .009). We find genetically driven social structure, or high relatedness among social units and clusters ( p .001), and a positive relationship between relatedness and association between individuals ( p .0001). Further, socially organized clusters are genetically distinct, indicating that social structure drives genetic divergence within the population, likely through restricted mate selection ( F ST p = .05). This genetic divergence among social groups can make the species less resilient to anthropogenic or ecological disturbance. Conservation of this species therefore depends on understanding links among social structure, genetic structure and ecological variability within the species.

Opposing mechanisms affect taxonomic convergence between tree assemblages during tropical forest succession - Natalia Norden; Vanessa Boukili; Anne Chao; K. H. Ma; Susan G. Letcher; Robin L. Chazdon (Ecology Letters, 2017)
Whether successional forests converge towards an equilibrium in species composition remains an elusive question, hampered by high idiosyncrasy in successional dynamics. Based on long‐term tree monitoring in second‐growth ( SG ) and old‐growth ( OG ) forests in Costa Rica, we show that patterns of convergence between pairs of forest stands depend upon the relative abundance of species exhibiting distinct responses to the successional gradient. For instance, forest generalists contributed to convergence between SG and OG forests, whereas rare species and old‐growth specialists were a source of divergence. Overall, opposing trends in taxonomic similarity among different subsets of species nullified each other, producing a net outcome of stasis over time. Our results offer an explanation for the limited convergence observed between pairwise communities and suggest that rare species and old‐growth specialists may be prone to dispersal limitation, while the dynamics of generalists and second‐growth specialists are more predictable, enhancing resilience in tropical secondary forests.

Metal-contaminated potato crops and potential human health risk in Bolivian mining highlands - Alan E. Garrido; William H. J. Strosnider; Robin Taylor Wilson; Janette Condori; Robert W. Nairn (Environmental Geochemistry and Health, 2017)

A Generic Multi-Compartmental CNS Distribution Model Structure for 9 Drugs Allows Prediction of Human Brain Target Site Concentrations - Yumi Yamamoto; Pyry A. Välitalo; Dirk-Jan van den Berg; Robin Hartman; Willem van den Brink; Yin Cheong Wong; Dymphy R. Huntjens; Johannes H. Proost; An Vermeulen; Walter Krauwinkel; Suruchi Bakshi; Vincent Aranzana-Climent; et al. (Pharmaceutical Research, 2017)

Proceedings of the third international molecular pathological epidemiology (MPE) meeting - Peter T. Campbell; Timothy R. Rebbeck; Reiko Nishihara; Andrew H. Beck; Colin B. Begg; Alexei A. Bogdanov; Yin Cao; Helen G. Coleman; Gordon J. Freeman; Yujing J. Heng; Curtis Huttenhower; Rafael A. Irizarry; et al. (Cancer Causes & Control, 2017)

Spatial Variation of Pressure in the Lyophilization Product Chamber Part 2: Experimental Measurements and Implications for Scale-up and Batch Uniformity - Pooja Sane; Nikhil Varma; Arnab Ganguly; Michael Pikal; Alina Alexeenko; Robin H. Bogner (AAPS PharmSciTech, 2017)

Estimates of local biodiversity change over time stand up to scrutiny - Mark Vellend; Maria Dornelas; Lander Baeten; Robin Beauséjour; Carissa D. Brown; Pieter De Frenne; Sarah C. Elmendorf; Nicholas J. Gotelli; Faye Moyes; Isla H. Myers‐Smith; Anne E. Magurran; Brian J. McGill; et al. (Ecology, 2017)
We present new data and analyses revealing fundamental flaws in a critique of two recent meta‐analyses of local‐scale temporal biodiversity change. First, the conclusion that short‐term time series lead to biased estimates of long‐term change was based on two errors in the simulations used to support it. Second, the conclusion of negative relationships between temporal biodiversity change and study duration was entirely dependent on unrealistic model assumptions, the use of a subset of data, and inclusion of one outlier data point in one study. Third, the finding of a decline in local biodiversity, after eliminating post‐disturbance studies, is not robust to alternative analyses on the original data set, and is absent in a larger, updated data set. Finally, the undebatable point, noted in both original papers, that studies in the ecological literature are geographically biased, was used to cast doubt on the conclusion that, outside of areas converted to croplands or asphalt, the distribution of biodiversity trends is centered approximately on zero. Future studies may modify conclusions, but at present, alternative conclusions based on the geographic‐bias argument rely on speculation. In sum, the critique raises points of uncertainty typical of all ecological studies, but does not provide an evidence‐based alternative interpretation.

Widespread Distribution of Dehalococcoides mccartyi in the Houston Ship Channel and Galveston Bay, Texas, Sediments and the Potential for Reductive Dechlorination of PCDD/F in an Estuarine Environment - Anne-Sophie Charlotte Hieke; Robin Brinkmeyer; Kevin M. Yeager; Kimberly Schindler; Saijin Zhang; Chen Xu; Patrick Louchouarn; Peter H. Santschi (Marine Biotechnology, 2016)

On the sustainability of inland fisheries: Finding a future for the forgotten - Steven J. Cooke; Edward H. Allison; T. Douglas Beard; Robert Arlinghaus; Angela H. Arthington; Devin M. Bartley; Ian G. Cowx; Carlos Fuentevilla; Nancy J. Leonard; Kai Lorenzen; Abigail J. Lynch; Vivian M. Nguyen; et al. (Ambio, 2016)

Fern species richness and abundance are indicators of climate change on high-elevation islands: evidence from an elevational gradient on Tahiti (French Polynesia) - Robin Pouteau; Jean-Yves Meyer; Pauline Blanchard; Joel H. Nitta; Maruiti Terorotua; Ravahere Taputuarai (Climatic Change, 2016)

When is a forest a forest? Forest concepts and definitions in the era of forest and landscape restoration - Robin L. Chazdon; Pedro H. S. Brancalion; Lars Laestadius; Aoife Bennett-Curry; Kathleen Buckingham; Chetan Kumar; Julian Moll-Rocek; Ima Célia Guimarães Vieira; Sarah Jane Wilson (Ambio, 2016)

Differential frequency of NKG2C/KLRC2 deletion in distinct African populations and susceptibility to Trachoma: a new method for imputation of KLRC2 genotypes from SNP genotyping data - Adriana Goncalves; Pateh Makalo; Hassan Joof; Sarah Burr; Athumani Ramadhani; Patrick Massae; Aiweda Malisa; Tara Mtuy; Tamsyn Derrick; Anna R. Last; Meno Nabicassa; Eunice Cassama; et al. (Human Genetics, 2016)

Context dependent bias in honeybee queen selection: swarm versus emergency queens - H. Michael G. Lattorff; Robin F. A. Moritz (Behavioral Ecology and Sociobiology, 2016)

Down-regulation of Arabidopsis DND1 orthologs in potato and tomato leads to broad-spectrum resistance to late blight and powdery mildew - Kaile Sun; Anne-Marie A. Wolters; Annelies E. H. M. Loonen; Robin P. Huibers; René van der Vlugt; Aska Goverse; Evert Jacobsen; Richard G. F. Visser; Yuling Bai (Transgenic Research, 2016)

Near-miss events, risk messages, and decision making - Robin L. Dillon; Catherine H. Tinsley (Environment Systems and Decisions, 2016)

Invasive plants have different effects on trophic structure of green and brown food webs in terrestrial ecosystems: a meta‐analysis - Matthew A. McCary; Robin Mores; Monica A. Farfan; David H. Wise (Ecology Letters, 2016)
Although invasive plants are a major source of terrestrial ecosystem degradation worldwide, it remains unclear which trophic levels above the base of the food web are most vulnerable to plant invasions. We performed a meta‐analysis of 38 independent studies from 32 papers to examine how invasive plants alter major groupings of primary and secondary consumers in three globally distributed ecosystems: wetlands, woodlands and grasslands. Within each ecosystem we examined if green (grazing) food webs are more sensitive to plant invasions compared to brown (detrital) food webs. Invasive plants have strong negative effects on primary consumers (detritivores, bacterivores, fungivores, and/or herbivores) in woodlands and wetlands, which become less abundant in both green and brown food webs in woodlands and green webs in wetlands. Plant invasions increased abundances of secondary consumers (predators and/or parasitoids) only in woodland brown food webs and green webs in wetlands. Effects of invasive plants on grazing and detrital food webs clearly differed between ecosystems. Overall, invasive plants had the most pronounced effects on the trophic structure of wetlands and woodlands, but caused no detectable changes to grassland trophic structure.

Variation in vervet (Chlorocebus aethiops) hair cortisol concentrations reflects ecological disturbance by humans - Nicolaas H. Fourie; Trudy R. Turner; Janine L. Brown; James D. Pampush; Joseph G. Lorenz; Robin M. Bernstein (Primates, 2015)

The effects of foundation species on community assembly: a global study on alpine cushion plant communities - Zaal Kikvidze; Robin W. Brooker; Bradley J. Butterfield; Ragan M. Callaway; Lohengrin A. Cavieres; Bradley J. Cook; Christopher J. Lortie; Richard Michalet; Francisco I. Pugnaire; Sa Xiao; Fabien Anthelme; Robert G. Björk; et al. (Ecology, 2015)
Foundation species can change plant community structure by modulating important ecological processes such as community assembly, yet this topic is poorly understood. In alpine systems, cushion plants commonly act as foundation species by ameliorating local conditions. Here, we analyze diversity patterns of species' assembly within cushions and in adjacent surrounding open substrates (83 sites across five continents) calculating floristic dissimilarity between replicate plots, and using linear models to analyze relationships between microhabitats and species diversity. Floristic dissimilarity did not change across biogeographic regions, but was consistently lower in the cushions than in the open microhabitat. Cushion plants appear to enable recruitment of many relatively stress‐intolerant species that otherwise would not establish in these communities, yet the niche space constructed by cushion plants supports a more homogeneous composition of species than the niche space beyond the cushion's influence. As a result, cushion plants support higher α‐diversity and a larger species pool, but harbor assemblies with lower β‐diversity than open microhabitats. We conclude that habitats with and without dominant foundation species can strongly differ in the processes that drive species recruitment, and thus the relationship between local and regional species diversity.

Mathematical Models to Explore Potential Effects of Supersaturation and Precipitation on Oral Bioavailability of Poorly Soluble Drugs - Mary S. Kleppe; Kelly M. Forney-Stevens; Roy J. Haskell; Robin H. Bogner (The AAPS Journal, 2015)

Variation of hair cortisol concentrations among wild populations of two baboon species (Papio anubis, P. hamadryas) and a population of their natural hybrids - Nicolaas H. Fourie; Clifford J. Jolly; Jane E. Phillips-Conroy; Janine L. Brown; Robin M. Bernstein (Primates, 2015)

Reply to “Letter to the Editor: Consistency Among Musculoskeletal Models: Caveat Utilitor” - David W. Wagner; Vahagn Stepanyan; James M. Shippen; Matthew S. DeMers; Robin S. Gibbons; Brian J. Andrews; Graham H. Creasey; Gary S. Beaupre (Annals of Biomedical Engineering, 2015)

Development of Action Thresholds for Management of Bactericera cockerelli and Zebra Chip Disease in Potatoes at Pukekohe, New Zealand - Graham P. Walker; Frances H. MacDonald; Peter J. Wright; Aleise J. Puketapu; Robin Gardner-Gee; Patrick G. Connolly; John A. D. Anderson (American Journal of Potato Research, 2015)

Nanomaterial risk screening: a structured approach to aid decision making under uncertainty - Christian E. H. Beaudrie; Milind Kandlikar; Robin Gregory; Graham Long; Tim Wilson (Environment Systems and Decisions, 2015)

Islands as model systems in ecology and evolution: prospects fifty years after MacArthur‐Wilson - Ben H. Warren; Daniel Simberloff; Robert E. Ricklefs; Robin Aguilée; Fabien L. Condamine; Dominique Gravel; Hélène Morlon; Nicolas Mouquet; James Rosindell; Juliane Casquet; Elena Conti; Josselin Cornuault; et al. (Ecology Letters, 2015)
The study of islands as model systems has played an important role in the development of evolutionary and ecological theory. The 50th anniversary of MacArthur and Wilson's (December 1963) article, ‘An equilibrium theory of insular zoogeography’, was a recent milestone for this theme. Since 1963, island systems have provided new insights into the formation of ecological communities. Here, building on such developments, we highlight prospects for research on islands to improve our understanding of the ecology and evolution of communities in general. Throughout, we emphasise how attributes of islands combine to provide unusual research opportunities, the implications of which stretch far beyond islands. Molecular tools and increasing data acquisition now permit re‐assessment of some fundamental issues that interested MacArthur and Wilson. These include the formation of ecological networks, species abundance distributions, and the contribution of evolution to community assembly. We also extend our prospects to other fields of ecology and evolution – understanding ecosystem functioning, speciation and diversification – frequently employing assets of oceanic islands in inferring the geographic area within which evolution has occurred, and potential barriers to gene flow. Although island‐based theory is continually being enriched, incorporating non‐equilibrium dynamics is identified as a major challenge for the future.

Activation tagging of ATHB13 in Arabidopsis thaliana confers broad-spectrum disease resistance - Dongli Gao; Michela Appiano; Robin P. Huibers; Xi Chen; Annelies E. H. M. Loonen; Richard G. F. Visser; Anne -Marie A. Wolters; Yuling Bai (Plant Molecular Biology, 2014)

Transient climate changes in a perturbed parameter ensemble of emissions-driven earth system model simulations - James M. Murphy; Ben B. B. Booth; Chris A. Boulton; Robin T. Clark; Glen R. Harris; Jason A. Lowe; David M. H. Sexton (Climate Dynamics, 2014)

Erection of the haploporid genus Litosaccus n. g. and its phylogenetic relationship within the Haploporidae Nicoll, 1914 - Michael J. Andres; Eric E. Pulis; Thomas H. Cribb; Robin M. Overstreet (Systematic Parasitology, 2014)

Outer Membrane Protein F Stabilised with Minimal Amphipol Forms Linear Arrays and LPS-Dependent 2D Crystals - Wanatchaporn Arunmanee; J. Robin Harris; Jeremy H. Lakey (The Journal of Membrane Biology, 2014)

Diurnal Variation in P-glycoprotein-Mediated Transport and Cerebrospinal Fluid Turnover in the Brain - Laura Kervezee; Robin Hartman; Dirk-Jan van den Berg; Shinji Shimizu; Yumi Emoto-Yamamoto; Johanna H. Meijer; Elizabeth C. M. de Lange (The AAPS Journal, 2014)

Mud, muddle and models in the knowledge value-chain to action on tropical peatland conservation - Meine van Noordwijk; Robin Matthews; Fahmuddin Agus; Jenny Farmer; Louis Verchot; Kristell Hergoualc’h; Sebastian Persch; Hesti Lestari Tata; Betha Lusiana; Atiek Widayati; Sonya Dewi (Mitigation and Adaptation Strategies for Global Change, 2014)

Implementing REDD+ (Reducing Emissions from Deforestation and Degradation): evidence on governance, evaluation and impacts from the REDD-ALERT project - Robin B. Matthews; Meine van Noordwijk; Eric Lambin; Patrick Meyfroidt; Joyeeta Gupta; Louis Verchot; Kristell Hergoualc’h; Edzo Veldkamp (Mitigation and Adaptation Strategies for Global Change, 2014)

Can leg ulcer fibroblasts phenotype be influenced by human amniotic membrane extract? - H. Tauzin; S. Robin; P. Humbert; C. Viennet; P. Saas; C. Courderot-Masuyer; P. Muret (Cell and Tissue Banking, 2014)

Temporal evolution and vertical stratification of Microcystis toxic potential during a first bloom event - H. Ait Hammou; D. Latour; M. Sabart; S. Samoudi; Kh. Mouhri; J. Robin; M. Loudiki (Aquatic Ecology, 2014)

Moving Rio Forward and Avoiding 10 More Years with Little Evidence for Effective Conservation Policy - BRENDAN FISHER; ANDREW BALMFORD; PAUL J. FERRARO; LOUISE GLEW; MICHAEL MASCIA; ROBIN NAIDOO; TAYLOR H. RICKETTS (Conservation Biology, 2014)

Climate change effects on animal and plant phylogenetic diversity in southern Africa - Dorothea V. Pio; Robin Engler; H. Peter Linder; Ara Monadjem; Fenton P.D. Cotterill; Peter J. Taylor; M. Corrie Schoeman; Benjamin W. Price; Martin H. Villet; Geeta Eick; Nicolas Salamin; Antoine Guisan (Global Change Biology, 2014)
Much attention has been paid to the effects of climate change on species' range reductions and extinctions. There is however surprisingly little information on how climate change driven threat may impact the tree of life and result in loss of phylogenetic diversity ( PD ). Some plant families and mammalian orders reveal nonrandom extinction patterns, but many other plant families do not. Do these discrepancies reflect different speciation histories and does climate induced extinction result in the same discrepancies among different groups? Answers to these questions require representative taxon sampling. Here, we combine phylogenetic analyses, species distribution modeling, and climate change projections on two of the largest plant families in the Cape Floristic Region (Proteaceae and Restionaceae), as well as the second most diverse mammalian order in Southern Africa (Chiroptera), and an herbivorous insect genus ( Platypleura ) in the family Cicadidae to answer this question. We model current and future species distributions to assess species threat levels over the next 70 years, and then compare projected with random PD survival. Results for these animal and plant clades reveal congruence. PD losses are not significantly higher under predicted extinction than under random extinction simulations. So far the evidence suggests that focusing resources on climate threatened species alone may not result in disproportionate benefits for the preservation of evolutionary history.

Resistance reaction of gene introgressed lines against rice blast (Pyricularia oryzae) disease - B. Divya; S. Robin; R. Rabindran; H. Manjunath; P. Valarmathi; A. John Joel (Australasian Plant Pathology, 2014)

Enzyme activity of the PIP4K2A gene product polymorphism that is implicated in schizophrenia - Jonathan H. Clarke; Robin F. Irvine (Psychopharmacology, 2013)

“The Ekman Drain”: a conduit to the deep ocean for shelf material - John H. Simpson; Robin R. McCandliss (Ocean Dynamics, 2013)

Dynamic coastal dune spit: the impact of morphological change on dune slacks at Whiteford Burrows, South Wales, UK - N. S. Robins; K. Pye; H. Wallace (Journal of Coastal Conservation, 2013)

Milling plant and soil material in plastic tubes over-estimates carbon and under-estimates nitrogen concentrations - Stuart W. Smith; A. H. Jean Robertson; Andrew A. Meharg; Robin J. Pakeman; David Johnson; Sarah J. Woodin; René van der Wal (Plant and Soil, 2013)

Consistency Among Musculoskeletal Models: Caveat Utilitor - David W. Wagner; Vahagn Stepanyan; James M. Shippen; Matthew S. DeMers; Robin S. Gibbons; Brian J. Andrews; Graham H. Creasey; Gary S. Beaupre (Annals of Biomedical Engineering, 2013)

Susceptibility of Forests in the Northeastern USA to Nitrogen and Sulfur Deposition: Critical Load Exceedance and Forest Health - N. Duarte; L. H. Pardo; M. J. Robin-Abbott (Water, Air, & Soil Pollution, 2013)

Interactive effects of methylphenidate and alcohol on discrimination, conditioned place preference and motor coordination in C57BL/6J mice - William C. Griffin; Robin W. McGovern; Guinevere H. Bell; Patrick K. Randall; Lawrence D. Middaugh; Kennerly S. Patrick (Psychopharmacology, 2013)

Understanding the Limits of Large Datasets - Catherine M. Sanders; Sidney L. Saltzstein; Matthew M. Schultzel; Duy H. Nguyen; Helen Shi Stafford; Georgia Robins Sadler (Journal of Cancer Education, 2012)

Reference hydrologic networks II. Using reference hydrologic networks to assess climate-driven changes in streamflow - Donald H. Burn; Jamie Hannaford; Glenn A. Hodgkins; Paul H. Whitfield; Robin Thorne; Terry Marsh (Hydrological Sciences Journal, 2012)

Spontaneous Crystalline-to-Amorphous Phase Transformation of Organic or Medicinal Compounds in the Presence of Porous Media, Part 3: Effect of Moisture - Ken K. Qian; Dale E. Wurster; Robin H. Bogner (Pharmaceutical Research, 2012)

Impact of Residual Stretch and Remodeling on Collagen Engagement in Healthy and Pulmonary Hypertensive Calf Pulmonary Arteries at Physiological Pressures - Lian Tian; Steven R. Lammers; Philip H. Kao; Joseph A. Albietz; Kurt R. Stenmark; H. Jerry Qi; Robin Shandas; Kendall S. Hunter (Annals of Biomedical Engineering, 2012)

Dry Powder Inhalers: Study of the Parameters Influencing Adhesion and Dispersion of Fluticasone Propionate - V. N. P. Le; T. H. Hoang Thi; E. Robins; M. P. Flament (AAPS PharmSciTech, 2012)

The mechanics of bacterial cluster formation on plant leaf surfaces as revealed by bioreporter technology - Robin Tecon; Johan H. J. Leveau (Environmental Microbiology, 2012)
Summary Bacteria that colonize the leaves of terrestrial plants often occur in clusters whose size varies from a few to thousands of cells. For the formation of such bacterial clusters, two non‐mutually exclusive but very different mechanisms may be proposed: aggregation of multiple cells or clonal reproduction of a single cell. Here we assessed the contribution of both mechanisms on the leaves of bean plants that were colonized by the bacterium Pantoea agglomerans . In one approach, we used a mixture of green and red fluorescent P. agglomerans cells to populate bean leaves. We observed that this resulted in clusters made up of only one colour as well as two‐colour clusters, thus providing evidence for both mechanisms. Another P. agglomerans bioreporter, designed to quantify the reproductive success of bacterial colonizers by proxy to the rate at which green fluorescent protein is diluted from dividing cells, revealed that during the first hours on the leaf surface, many bacteria were dividing, but not staying together and forming clusters, which is suggestive of bacterial relocation. Together, these findings support a dynamic model of leaf surface colonization, where both aggregative and reproductive mechanisms take place. The bioreporter‐based approach we employed here should be broadly applicable towards a more quantitative and mechanistic understanding of bacterial colonization of surfaces in general.

Microdeletion/microduplication of proximal 15q11.2 between BP1 and BP2: a susceptibility region for neurological dysfunction including developmental and language delay - Rachel D. Burnside; Romela Pasion; Fady M. Mikhail; Andrew J. Carroll; Nathaniel H. Robin; Erin L. Youngs; Inder K. Gadi; Elizabeth Keitges; Vikram L. Jaswaney; Peter R. Papenhausen; Venkateswara R. Potluri; Hiba Risheg; et al. (Human Genetics, 2011)

Missense variants in hMLH1 identified in patients from the German HNPCC consortium and functional studies - Karin Hardt; Sven Boris Heick; Beate Betz; Timm Goecke; Haniyeh Yazdanparast; Robin Küppers; Kati Servan; Verena Steinke; Nils Rahner; Monika Morak; Elke Holinski-Feder; Christoph Engel; et al. (Familial Cancer, 2011)

Generation of Priority Research Questions to Inform Conservation Policy and Management at a National Level - MURRAY A. RUDD; KAREN F. BEAZLEY; STEVEN J. COOKE; ERICA FLEISHMAN; DANIEL E. LANE; MICHAEL B. MASCIA; ROBIN ROTH; GARY TABOR; JISELLE A. BAKKER; TERESA BELLEFONTAINE; DOMINIQUE BERTEAUX; BERNARD CANTIN; et al. (Conservation Biology, 2011)
Integrating knowledge from across the natural and social sciences is necessary to effectively address societal tradeoffs between human use of biological diversity and its preservation. Collaborative processes can change the ways decision makers think about scientific evidence, enhance levels of mutual trust and credibility, and advance the conservation policy discourse. Canada has responsibility for a large fraction of some major ecosystems, such as boreal forests, Arctic tundra, wetlands, and temperate and Arctic oceans. Stressors to biological diversity within these ecosystems arise from activities of the country's resource‐based economy, as well as external drivers of environmental change. Effective management is complicated by incongruence between ecological and political boundaries and conflicting perspectives on social and economic goals. Many knowledge gaps about stressors and their management might be reduced through targeted, timely research. We identify 40 questions that, if addressed or answered, would advance research that has a high probability of supporting development of effective policies and management strategies for species, ecosystems, and ecological processes in Canada. A total of 396 candidate questions drawn from natural and social science disciplines were contributed by individuals with diverse organizational affiliations. These were collaboratively winnowed to 40 by our team of collaborators. The questions emphasize understanding ecosystems, the effects and mitigation of climate change, coordinating governance and management efforts across multiple jurisdictions, and examining relations between conservation policy and the social and economic well‐being of Aboriginal peoples. The questions we identified provide potential links between evidence from the conservation sciences and formulation of policies for conservation and resource management. Our collaborative process of communication and engagement between scientists and decision makers for generating and prioritizing research questions at a national level could be a model for similar efforts beyond Canada.

The timing of sea ice formation and exposure to photosynthetically active radiation along the Western Antarctic Peninsula - Christian H. Fritsen; Jeramie C. Memmott; Robin M. Ross; Langdon B. Quetin; Maria Vernet; Eric D. Wirthlin (Polar Biology, 2011)

Social parasitism of queens and workers in the Cape honeybee (Apis mellifera capensis) - Robin F. A. Moritz; H. Michael G. Lattorff; Kendall L. Crous; Randall H. Hepburn (Behavioral Ecology and Sociobiology, 2011)

Solubility Advantage of Amorphous Pharmaceuticals: II. Application of Quantitative Thermodynamic Relationships for Prediction of Solubility Enhancement in Structurally Diverse Insoluble Pharmaceuticals - Sharad B. Murdande; Michael J. Pikal; Ravi M. Shanker; Robin H. Bogner (Pharmaceutical Research, 2010)

Apes in a changing world – the effects of global warming on the behaviour and distribution of African apes - Julia Lehmann; Amanda H. Korstjens; Robin I. M. Dunbar (Journal of Biogeography, 2010)
Aim In this study we use a modelling approach to identify: (1) the factors responsible for the differences in ape biogeography, (2) the effects that global warming might have on distribution patterns of African apes, (3) the underlying mechanisms for these effects, and (4) the implications that behavioural flexibility might be expected to have for ape survival. All African apes are highly endangered, and the need for efficient conservation methods is a top priority. The expected changes in world climate are likely to further exacerbate the difficulties they face. Our study aims to further understand the mechanisms that link climatic conditions to the behaviour and biogeography of ape species. Location Africa. Method We use an existing validated time budgets model, derived from data on 20 natural populations of gorillas ( Gorilla beringei and Gorilla gorilla ) and chimpanzees ( Pan troglodytes and Pan paniscus ), which specifies the relationship between climate, group size, body weight and time available for various activities, to predict ape distribution across Africa under a uniform worst‐case climate change scenario. Results We demonstrate that a worst‐case global warming scenario is likely to alter the delicate balance between different time budget components. Our model points to the importance of annual temperature variation, which was found to have the strongest impact on ape biogeography. Our simulation indicates that rising temperatures and changes in rainfall patterns are likely to have strong effects on ape survival and distribution, particularly for gorillas. Even if they behaved with maximum flexibility, gorillas may not be able to survive in most of their present habitats if the climate was to undergo extreme changes. The survival of chimpanzees was found to be strongly dependent on the minimum viable group size required. Main conclusions Our model allows us to explore how climatic conditions, individual behaviour and morphological traits may interact to limit the biogeographical distributions of these species, thereby allowing us to predict the effects of climate change on African ape distributions under different climate change regimes. The model suggests that climate variability (i.e. seasonality) plays a more important role than the absolute magnitude of the change, but these data are not normally provided by climate models.

Female-biased incubation and strong diel sex-roles in the Two-banded Plover Charadrius falklandicus - James J. H. St Clair; Philipp Herrmann; Robin W. Woods; Tamás Székely (Journal of Ornithology, 2010)

Divergent composition but similar function of soil food webs of individual plants: plant species and community effects - T. M. Bezemer; M. T. Fountain; J. M. Barea; S. Christensen; S. C. Dekker; H. Duyts; R. van Hal; J. A. Harvey; K. Hedlund; M. Maraun; J. Mikola; A. G. Mladenov; et al. (Ecology, 2010)
Soils are extremely rich in biodiversity, and soil organisms play pivotal roles in supporting terrestrial life, but the role that individual plants and plant communities play in influencing the diversity and functioning of soil food webs remains highly debated. Plants, as primary producers and providers of resources to the soil food web, are of vital importance for the composition, structure, and functioning of soil communities. However, whether natural soil food webs that are completely open to immigration and emigration differ underneath individual plants remains unknown. In a biodiversity restoration experiment we first compared the soil nematode communities of 228 individual plants belonging to eight herbaceous species. We included grass, leguminous, and non‐leguminous species. Each individual plant grew intermingled with other species, but all plant species had a different nematode community. Moreover, nematode communities were more similar when plant individuals were growing in the same as compared to different plant communities, and these effects were most apparent for the groups of bacterivorous, carnivorous, and omnivorous nematodes. Subsequently, we analyzed the composition, structure, and functioning of the complete soil food webs of 58 individual plants, belonging to two of the plant species, Lotus corniculatus (Fabaceae) and Plantago lanceolata (Plantaginaceae). We isolated and identified more than 150 taxa/groups of soil organisms. The soil community composition and structure of the entire food webs were influenced both by the species identity of the plant individual and the surrounding plant community. Unexpectedly, plant identity had the strongest effects on decomposing soil organisms, widely believed to be generalist feeders. In contrast, quantitative food web modeling showed that the composition of the plant community influenced nitrogen mineralization under individual plants, but that plant species identity did not affect nitrogen or carbon mineralization or food web stability. Hence, the composition and structure of entire soil food webs vary at the scale of individual plants and are strongly influenced by the species identity of the plant. However, the ecosystem functions these food webs provide are determined by the identity of the entire plant community.

How Do Cancer Patients Navigate the Public Information Environment? Understanding Patterns and Motivations for Movement Among Information Sources - Rebekah H. Nagler; Anca Romantan; Bridget J. Kelly; Robin S. Stevens; Stacy W. Gray; Shawnika J. Hull; A. Susana Ramirez; Robert C. Hornik (Journal of Cancer Education, 2010)

Health Journalism Internships: A Social Marketing Strategy to Address Health Disparities - Duy H. Nguyen; Suzuho Shimasaki; Helen Shi Stafford; Georgia Robins Sadler (Journal of Cancer Education, 2010)

Abundance and survival rates of green turtles in an urban environment: coexistence of humans and an endangered species - Tomoharu Eguchi; Jeffrey A. Seminoff; Robin A. LeRoux; Peter H. Dutton; Donna L. Dutton (Marine Biology, 2010)

The Holocene Pucón eruption of Volcán Villarrica, Chile: deposit architecture and eruption chronology - C. Silva Parejas; T. H. Druitt; C. Robin; H. Moreno; J.-A. Naranjo (Bulletin of Volcanology, 2010)

Estimating the Density of Honeybee Colonies across Their Natural Range to Fill the Gap in Pollinator Decline Censuses - RODOLFO JAFFÉ; VINCENT DIETEMANN; MIKE H. ALLSOPP; CECILIA COSTA; ROBIN M. CREWE; RAFFAELE DALL’OLIO; PILAR DE LA RÚA; MOGBEL A. A. EL‐NIWEIRI; INGEMAR FRIES; NIKOLA KEZIC; MICHAEL S. MEUSEL; ROBERT J. PAXTON; et al. (Conservation Biology, 2010)
Although pollinator declines are a global biodiversity threat, the demography of the western honeybee ( Apis mellifera ) has not been considered by conservationists because it is biased by the activity of beekeepers. To fill this gap in pollinator decline censuses and to provide a broad picture of the current status of honeybees across their natural range, we used microsatellite genetic markers to estimate colony densities and genetic diversity at different locations in Europe, Africa, and central Asia that had different patterns of land use. Genetic diversity and colony densities were highest in South Africa and lowest in Northern Europe and were correlated with mean annual temperature. Confounding factors not related to climate, however, are also likely to influence genetic diversity and colony densities in honeybee populations. Land use showed a significantly negative influence over genetic diversity and the density of honeybee colonies over all sampling locations. In Europe honeybees sampled in nature reserves had genetic diversity and colony densities similar to those sampled in agricultural landscapes, which suggests that the former are not wild but may have come from managed hives. Other results also support this idea: putative wild bees were rare in our European samples, and the mean estimated density of honeybee colonies on the continent closely resembled the reported mean number of managed hives. Current densities of European honeybee populations are in the same range as those found in the adverse climatic conditions of the Kalahari and Saharan deserts, which suggests that beekeeping activities do not compensate for the loss of wild colonies. Our findings highlight the importance of reconsidering the conservation status of honeybees in Europe and of regarding beekeeping not only as a profitable business for producing honey, but also as an essential component of biodiversity conservation.

Release from bats: genetic distance and sensoribehavioural regression in the Pacific field cricket, Teleogryllus oceanicus - James H. Fullard; Hannah M. ter Hofstede; John M. Ratcliffe; Gerald S. Pollack; Gian S. Brigidi; Robin M. Tinghitella; Marlene Zuk (The Science of Nature, 2010)

Population structure of island-associated dolphins: Evidence from photo-identification of common bottlenose dolphins ( Tursiops truncatus ) in the main Hawaiian Islands - Robin W. Baird; Antoinette M. Gorgone; Daniel J. McSweeney; Allan D. Ligon; Mark H. Deakos; Daniel L. Webster; Gregory S. Schorr; Karen K. Martien; Dan R. Salden; Sabre D. Mahaffy (Marine Mammal Science, 2009)

Methods for estimating the amount of vernal pool habitat in the northeastern United States - Robin Meter; Larissa L. Bailey; Evan H. Campbell Grant (Wetlands, 2008)

Maintenance of cyanotoxin production by cryopreserved cyanobacteria in the New Zealand culture collection - Susanna A. Wood; Lesley L. Rhodes; Serean L. Adams; Janet E. Adamson; Kirsty F. Smith; John F. Smith; H. Robin Tervit; S. Craig Cary (New Zealand Journal of Marine and Freshwater Research, 2008)
A culture collection of freshwater planktonic and benthic cyanobacteria collected from sites across New Zealand has been established at the Cawthron Institute, Nelson, New Zealand. Limited resources led to uncertainty regarding the long‐term maintenance of this collection. The present study demonstrates cryopreservation to be a viable method for long‐term storage of cyanobacteria. Seventeen of 20 strains evaluated were successfully cryopreserved using the permeating cryopreservation agent dimethyl sulfoxide (Me 2 SO), at a final concentration of 15% (v/v). Cyanotoxin analysis was undertaken on selected strains known to produce microcystins, nodularin, anatoxin‐a, and saxitoxins. All strains retained their ability to produce these toxins following cryopreservation.

Explaining the global pattern of protected area coverage: relative importance of vertebrate biodiversity, human activities and agricultural suitability - Colby Loucks; Taylor H. Ricketts; Robin Naidoo; John Lamoreux; Jonathan Hoekstra (Journal of Biogeography, 2008)
Aim Twelve per cent of the Earth’s terrestrial surface is covered by protected areas, but neither these areas nor the biodiversity they contain are evenly distributed spatially. To guide future establishment of protected areas, it is important to understand the factors that have shaped the spatial arrangement of the current protected area system. We used an information‐theoretic approach to assess the ability of vertebrate biodiversity measures, resource consumption and agricultural potential to explain the global coverage pattern of protected areas. Location Global. Methods For each of 762 World Wildlife Fund terrestrial ecoregions of the world, we measured protected area coverage, resource consumption, terrestrial vertebrate species richness, number of endemic species, number of threatened species, net primary production, elevation and topographic heterogeneity. We combined these variables into 39 a priori models to describe protected area coverage at the global scale, and for six biogeographical realms. Using the Akaike information criterion and Akaike weights, we identified the relative importance and influence of each variable in describing protected area coverage. Results Globally, the number of endemic species was the best variable describing protected area coverage, followed by the number of threatened species. Species richness and resource consumption were of moderate importance and agricultural potential had weak support for describing protected area coverage at a global scale. Yet, the relative importance of these factors varied among biogeographical realms. Measures of vertebrate biodiversity (species richness, endemism and threatened species) were among the most important variables in all realms, except the Indo‐Malayan, but had a wide range of relative importance and influence. Resource consumption was inversely related to protected area coverage across all but one realm (the Palearctic), most strongly in the Nearctic realm. Agricultural potential, despite having little support in describing protected area coverage globally, was strongly and positively related to protection in the Palearctic and Neotropical realms, as well as in the Indo‐Malayan realm. The Afrotropical, Indo‐Malayan and Australasian realms showed no clear, strong relationships between protected area coverage and the independent variables. Main conclusions Globally, the existing protected area network is more strongly related to biodiversity measures than to patterns of resource consumption or agricultural potential. However, the relative importance of these factors varies widely among the world’s biogeographical realms. Understanding the biases of the current protected area system may help to correct for them as future protected areas are added to the global network.

False killer whales ( Pseudorca crassidens ) around the main Hawaiian Islands: Long‐term site fidelity, inter‐island movements, and association patterns - Robin W. Baird; Antoinette M. Gorgone; Daniel J. McSweeney; Daniel L. Webster; Dan R. Salden; Mark H. Deakos; Allan D. Ligon; Gregory S. Schorr; Jay Barlow; Sabre D. Mahaffy (Marine Mammal Science, 2008)
Despite their world‐wide distribution throughout the tropics and subtropics, false killer whales ( Pseudorca crassidens ) are one of the lesser‐known large odontocetes. Genetic evidence indicates a demographically isolated population around the main Hawaiian Islands. We examine site fidelity, movements and association patterns in this population using data from directed surveys and opportunistic photographs from 1986 to 2007. This species was only infrequently encountered, and while found in depths from 38 to 4,331 m, sighting rates were greatest in depths >3,000 m. We photo‐identified 152 distinctive individuals. Resighting rates were high, with an average of 76.8% of distinctive individuals within groups documented on more than one occasion. Most (86.6%) were linked by association into a single social network; only one large group (16 distinctive individuals), documented the farthest offshore (42–70 km), did not link by association to that large network, and may be part of an offshore population. Individual movements of up to 283 km were documented, with a large proportion of individuals moving among islands. Individuals were resighted up to 20.1 yr after first being documented, showing long‐term fidelity to the islands. Repeated associations among individuals were documented for up to 15 yr, and association analyses indicate preferred associations and strong bonds among individuals.

Senescence rates are determined by ranking on the fast–slow life‐history continuum - Owen R. Jones; Jean‐Michel Gaillard; Shripad Tuljapurkar; Jussi S. Alho; Kenneth B. Armitage; Peter H. Becker; Pierre Bize; Jon Brommer; Anne Charmantier; Marie Charpentier; Tim Clutton‐Brock; F. Stephen Dobson; et al. (Ecology Letters, 2008)
Comparative analyses of survival senescence by using life tables have identified generalizations including the observation that mammals senesce faster than similar‐sized birds. These generalizations have been challenged because of limitations of life‐table approaches and the growing appreciation that senescence is more than an increasing probability of death. Without using life tables, we examine senescence rates in annual individual fitness using 20 individual‐based data sets of terrestrial vertebrates with contrasting life histories and body size. We find that senescence is widespread in the wild and equally likely to occur in survival and reproduction. Additionally, mammals senesce faster than birds because they have a faster life history for a given body size. By allowing us to disentangle the effects of two major fitness components our methods allow an assessment of the robustness of the prevalent life‐table approach. Focusing on one aspect of life history – survival or recruitment – can provide reliable information on overall senescence.

Short-sighted evolution of virulence in parasitic honeybee workers (Apis mellifera capensis Esch.) - Robin F. A. Moritz; Christian W. W. Pirk; H. Randall Hepburn; Peter Neumann (The Science of Nature, 2008)

Recombination Rate and AT-content Show Opposite Correlations in Mammalian and Other Animal Genomes - H. Michael G. Lattorff; Robin F. A. Moritz (Evolutionary Biology, 2008)

In situ analysis by microspectroscopy reveals triterpenoid compositional patterns within leaf cuticles of Prunus laurocerasus - Marcia M. L. Yu; Stanislav O. Konorov; H. Georg Schulze; Michael W. Blades; Robin F. B. Turner; Reinhard Jetter (Planta, 2008)

Antibiotic and Disinfectant Susceptibility Profiles of Vancomycin-Resistant Enterococcus faecium (VRE) Isolated from Community Wastewater in Texas - Ross C. Beier; Sara E. Duke; Richard L. Ziprin; Roger B. Harvey; Michael E. Hume; Toni L. Poole; H. Morgan Scott; Linda D. Highfield; Walid Q. Alali; Kathleen Andrews; Robin C. Anderson; David J. Nisbet (Bulletin of Environmental Contamination and Toxicology, 2008)

Amorphization Alone Does Not Account for the Enhancement of Solubility of Drug Co-ground with Silicate: The Case of Indomethacin - Deepak Bahl; Robin H. Bogner (AAPS PharmSciTech, 2008)

Solventless photocurable film coating: Evaluation of drug release, mechanical strength, and photostability - Sagarika Bose; Robin H. Bogner (AAPS PharmSciTech, 2007)

Phosphylated tyrosine in albumin as a biomarker of exposure to organophosphorus nerve agents - Nichola H. Williams; John M. Harrison; Robert W. Read; Robin M. Black (Archives of Toxicology, 2007)

Hypotaurine and thiotaurine as indicators of sulfide exposure in bivalves and vestimentiferans from hydrothermal vents and cold seeps - Garth L. Brand; Robin V. Horak; Nadine Le Bris; Shana K. Goffredi; Susan L. Carney; Breea Govenar; Paul H. Yancey (Marine Ecology, 2007)
Vesicomyid clams, vestimentiferans, and some bathymodiolin mussels from hydrothermal vents and cold seeps possess thiotrophic endosymbionts, high levels of hypotaurine and, in tissues with symbionts, thiotaurine. The latter, a product of hypotaurine and sulfide, may store and/or transport sulfide non‐toxically, and the ratio to hypotaurine plus thiotaurine (Th/[H + Th]) may reflect an animal's sulfide exposure. To test this, we analyzed seep and vent animals with in situ sulfide measurements. Calyptogena kilmeri clams occur at high‐sulfide seeps in Monterey Canyon, while C. (Vesicomya) pacifica clams occur at seeps with lower levels but take up and metabolize sulfide more effectively. From one seep where they co‐occur, both had gill thiotaurine contents at 22–25 mmol kg −1 wet mass, and while C. (V.) pacifica had a higher blood sulfide level, it had a lower Th/[H + Th] (0.39) than C. kilmeri (0.63). However, these same species from different seeps with lower sulfide exposures had lower ratios. Bathymodiolus thermophilus [East Pacific Rise (EPR 9°50′ N)] from high‐(84 μ m ) and a low‐(7 μ m ) sulfide vents had gill ratios of 0.40 and 0.12, respectively. Trophosomes of Riftia pachyptila (EPR 9°50′ N) from medium‐(33 μ m ) and low‐(4 μ m ) sulfide vents had ratios of 0.23 and 0.20, respectively (not significantly different). Ridgeia piscesae vestimentiferans (Juan de Fuca Ridge) have very different phenotypes at high‐ and low‐sulfide sites, and their trophosomes had the greatest differences: 0.81 and 0.04 ratios from high‐ and low‐sulfide sites, respectively. Thus Th/[H + Th] may indicate sulfide exposure levels within species, but not in interspecies comparisons, possibly due to phylogenetic and metabolic differences. Total H + Th was constant within each species (except in R. piscesae ); the sum may indicate the maximum potential sulfide load that a species faces.

Amorphization of Indomethacin by Co-Grinding with Neusilin US2: Amorphization Kinetics, Physical Stability and Mechanism - Deepak Bahl; Robin H. Bogner (Pharmaceutical Research, 2006)

Design space for a solventless photocurable pharmaceutical coating - Sagarika Bose; Brendan Kelly; Robin H. Bogner (Journal of Pharmaceutical Innovation, 2006)

A maternal hypomethylation syndrome presenting as transient neonatal diabetes mellitus - D. J. G. Mackay; S. E. Boonen; J. Clayton-Smith; J. Goodship; J. M. D. Hahnemann; S. G. Kant; P. R. Njølstad; N. H. Robin; D. O. Robinson; R. Siebert; J. P. H. Shield; H. E. White; et al. (Human Genetics, 2006)

Time as a constraint on group size in spider monkeys - Amanda H. Korstjens; Ingrid Lugo Verhoeckx; Robin I. M. Dunbar (Behavioral Ecology and Sociobiology, 2006)

Rare royal families in honeybees, Apis melliferas - Robin F. A. Moritz; H. Michael; G. Lattorff; Peter Neumann; F. Bernhard Kraus; Sarah E. Radloff; H. Randall Hepburn (The Science of Nature, 2005)

Oil pollution and climate have wide‐scale impacts on seabird demographics - Stephen C. Votier; Ben J. Hatchwell; Andrew Beckerman; Robin H. McCleery; Fiona M. Hunter; Jayne Pellatt; Mark Trinder; Tim R. Birkhead (Ecology Letters, 2005)
Oil spills often spell disaster for marine birds caught in slicks. However, the impact of oil pollution on seabird population parameters is poorly known because oil spills usually occur in wintering areas remote from breeding colonies where birds may be distributed over a wide area, and because it is difficult to separate the effects of oil pollution from the effect of natural environmental variation on seabird populations. Using a long‐term data set we show that over‐winter survival of adult common guillemots ( Uria aalge ) is negatively affected by both the incidence of four major oil‐spills in their wintering grounds and high values of the North Atlantic Oscillation (NAO) index. After controlling for the effect of the NAO index, we show that winter mortality of adult guillemots is doubled by major oil pollution incidents. Our results demonstrate that oil pollution can have wide‐scale impacts on marine ecosystems that can be quantified using populations of marked individuals to estimate survival.

Rare royal families in honeybees, Apis mellifera - Robin F. A. Moritz; H. Michael G. Lattorff; Peter Neumann; F. Bernhard Kraus; Sarah E. Radloff; H. Randall Hepburn (The Science of Nature, 2005)

Double-observer approach to estimating egg mass abundance of pool-breeding amphibians - Evan H. Campbell Grant; Robin E. Jung; James D. Nichols; James E. Hines (Wetlands Ecology and Management, 2005)

Tolerance of wheat (Triticum aestivum L.) to high soil and solution selenium levels - Graham H. Lyons; James C. R. Stangoulis; Robin D. Graham (Plant and Soil, 2005)

Influence of dry diets on reproductive performance and egg lipid composition during the first spawning season of captive pollack - M. H. Omnes; S. Recek; H. Barone; H. Le Delliou; A. Schmitz; A. Mutelet; M. Suquet; J. H. Robin (Journal of Fish Biology, 2004)
Four‐year‐old pollack Pollachius pollachius L., previously fed on dry pellets since their juvenile stage, were divided into three experimental groups two months prior their first spawning season. They were fed a commercial broodstock pellet enriched with 6% added oils, either: (1) capelin oil (control), (2) capelin oil plus arachidonic acid, or (3) DHA rich tuna oil. Spawning performance was determined in each group and egg lipids were analysed. During the vitellogenic period, the estradiol levels in plasma increased with oocyte enlargement, indicating that captivity and pelleted feed did not affect reproductive capacity. Females from each group spawned spontaneously between February and May. Egg production per kg of female was highest in the control group. Fertilization rate was highest (39%) in the group fed on diet enhanced in DHA. Lipid content in eggs reached 16% of dry mass, containing mainly phospholipids (75%). Egg fatty acid profiles showed few differences between dietary treatments. There was no significant difference in the concentration of Docosahexaenoic acid (22:6n − 3) between groups. Arachidonic acid (20:4n − 6) was lower in neutral and polar lipids of eggs from the control group than in the other groups. Tuna oil diet induced the highest DHA/EPA ratio in eggs and seemed to provide sufficient arachidonic acid for pollack broodstock. Egg fatty acid profiles are compared with 6 year‐old pollack broodstock fed on fish, and with other cultured and wild fish species.

Expansion of human settlement in Kenya's Maasai Mara: what future for pastoralism and wildlife? - Richard H. Lamprey; Robin S. Reid (Journal of Biogeography, 2004)
Aim Wildlife and pastoral peoples have lived side‐by‐side in the Mara ecosystem of south‐western Kenya for at least 2000 years. Recent changes in human population and landuse are jeopardizing this co‐existence. The aim of the study is to determine the viability of pastoralism and wildlife conservation in Maasai ranches around the Maasai Mara National Reserve (MMNR). Location A study area of 2250 km 2 was selected in the northern part of the Serengeti‐Mara ecosystem, encompassing group ranches adjoining the MMNR. Emphasis is placed on Koyake Group Ranch, a rangeland area owned by Maasai pastoralists, and one of Kenya's major wildlife tourism areas. Methods Maasai settlement patterns, vegetation, livestock numbers and wildlife numbers were analysed over a 50‐year period. Settlement distributions and vegetation changes were determined from aerial photography and aerial surveys of 1950, 1961, 1967, 1974, 1983 and 1999. Livestock and wildlife numbers were determined from re‐analysis of systematic reconnaissance flights conducted by the Kenya Government from 1977 to 2000, and from ground counts in 2002. Corroborating data on livestock numbers were obtained from aerial photography of Maasai settlements in 2001. Trends in livestock were related to rainfall, and to vegetation production as indicated by the seasonal Normalized Difference Vegetation Index. With these data sets, per capita livestock holdings were determined for the period 1980–2000, a period of fluctuating rainfall and primary production. Results For the first half of the twentieth century, the Mara was infested with tsetse‐flies, and the Maasai were confined to the Lemek Valley area to the north of the MMNR. During the early 1960s, active tsetse‐control measures by both government and the Maasai led to the destruction of woodlands across the Mara and the retreat of tsetse flies. The Maasai were then able to expand their settlement area south towards MMNR. Meanwhile, wildebeest ( Connochaetes taurinus ) from the increasing Serengeti population began to spill into the Mara rangelands each dry season, leading to direct competition between livestock and wildlife. Group ranches were established in the area in 1970 to formalize land tenure for the Maasai. By the late 1980s, with rapid population growth, new settlement areas had been established at Talek and other parts adjacent to the MMNR. Over the period 1983–99, the number of Maasai bomas in Koyake has increased at 6.4% per annum (pa), and the human population at 4.4% pa. Over the same period, cattle numbers on Koyake varied from 20,000 to 45,000 (average 25,000), in relation to total rainfall received over the previous 2 years. The rangelands of the Mara cannot support a greater cattle population under current pastoral practices. Conclusions With the rapid increase in human settlement in the Mara, and with imminent land privatization, it is probable that wildlife populations on Koyake will decline significantly in the next 3–5 years. Per capita livestock holdings on the ranch have now fallen to three livestock units/reference adult, well below minimum pastoral subsistence requirements. During the 1980s and 90s the Maasai diversified their livelihoods to generate revenues from tourism, small‐scale agriculture and land‐leases for mechanized cultivation. However, there is a massive imbalance in tourism incomes in favour of a small elite. In 1999 the membership of Koyake voted to subdivide the ranch into individual holdings. In 2003 the subdivision survey allocated plots of 60 ha average size to 1020 ranch members. This land privatization may result in increased cultivation and fencing, the exclusion of wildlife, and the decline of tourism as a revenue generator. This unique pastoral/wildlife system will shortly be lost unless land holdings can be managed to maintain the free movement of livestock and wildlife.

Nitrogen Limits an Invasive Perennial Shrub in Forest Understory - Timothy M. Cassidy; James H. Fownes; Robin A. Harrington (Biological Invasions, 2004)

Mapping osmotic adjustment in an advanced back-cross inbred population of rice - S. Robin; M. S. Pathan; B. Courtois; R. Lafitte; S. Carandang; S. Lanceras; M. Amante; H. T. Nguyen; Z. Li (Theoretical and Applied Genetics, 2003)

Geochemical stratigraphy of the lavas of the Solund-Stavfjord Ophiolite Complex, W. Norway, and magma-chamber dynamics - H. Furnes; B. Hellevang; B. Robins; A. Gudmundsson (Bulletin of Volcanology, 2003)

Paracrine role of soluble guanylate cyclase and type III nitric oxide synthase in ovine fetal pulmonary circulation: a double labeling immunohistochemical study - Ching Tzao; Peter A. Nickerson; James A. Russell; Bernice K. Noble; Robin H. Steinhorn (Histochemistry and Cell Biology, 2003)

Hydrogen Bonding with Adsorbent During Storage Governs Drug Dissolution from Solid-Dispersion Granules - Manish K. Gupta; Yin-Chao Tseng; David Goldman; Robin H. Bogner (Pharmaceutical Research, 2002)

Effect of DNA concentration on transgenesis rates in mice and pigs - Mark. B. Nottle; K.A. Haskard; P.J. Verma; Z.T. Du; C.G. Grupen; S.M. McIlfatrick; R.J. Ashman; S.J. Harrison; H. Barlow; P.L. Wigley; I.G. Lyons; P.J. Cowan; et al. (Transgenic Research, 2001)

Production and Resource Use Efficiencies in N- and P-Limited Tropical Forests: A Comparison of Responses to Long-term Fertilization - Robin A. Harrington; James H. Fownes; Peter M. Vitousek (Ecosystems, 2001)

Shifts in Social Structure of Black Howler (Alouatta pigra) Groups Associated with Natural and Experimental Variation in Population Density - Linde E. T. Ostro; Scott C. Silver; Fred W. Koontz; Robert H. Horwich; Robin Brockett (International Journal of Primatology, 2001)

Locating genomic regions associated with components of drought resistance in rice: comparative mapping within and across species - J. Zhang; H. G. Zheng; A. Aarti; G. Pantuwan; T. T. Nguyen; J. N. Tripathy; A. K. Sarial; S. Robin; R. C. Babu; Bay D. Nguyen; S. Sarkarung; A. Blum; et al. (Theoretical and Applied Genetics, 2001)

A molecular approach to dominance in hypophosphatasia - A. Lia-Baldini; F. Muller; A. Taillandier; J. Gibrat; M. Mouchard; B. Robin; B. Simon-Bouy; J. Serre; A. Aylsworth; E. Bieth; S. Delanote; P. Freisinger; et al. (Human Genetics, 2001)

Kinetic analysis of boron transport in Chara - James C. R. Stangoulis; Robert J. Reid; Patrick H. Brown; Robin D. Graham (Planta, 2001)

Elevational distribution of restricted range forest tree taxa in eastern Tanzania - Jon C. Lovett; G. Philip Clarke; Robin Moore; Gilbert H. Morrey (Biodiversity and Conservation, 2001)

Heterogeneous distribution of type I nitric oxide synthase in pulmonary vasculature of ovine fetus - Ching Tzao; Peter A. Nickerson; James A. Russell; Bernice K. Noble; Robin H. Steinhorn (Histochemistry and Cell Biology, 2000)

QTLs for cell-membrane stability mapped in rice (Oryza sativa L.) under drought stress - J. N. Tripathy; Jingxian Zhang; S. Robin; Thuy T. Nguyen; H. T. Nguyen (Theoretical and Applied Genetics, 2000)

Distribution and diversity of mtDNA lineages among southern right whales ( Eubalaena australis ) from Australia and New Zealand - C. S. Baker; N. J. Patenaude; J. L. Bannister; J. Robins; H. Kato (Marine Biology, 1999)

An Aquifer Management Case Study – The Chalk of the English South Downs - N. S. Robins; H. K. Jones; J. Ellis (Water Resources Management, 1999)

Combined effect of the growth temperature and salinity of the medium on the accumulation of compatible solutes by Rhodothermus marinus and Rhodothermus obamensis - Zélia Silva; Nuno Borges; Lígia O. Martins; Robin Wait; Milton S. da Costa; H. Santos (Extremophiles, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Molecular characterization and delineation of subtle deletions in de novo “balanced” chromosomal rearrangements - Arun Kumar; Laurie A. Becker; Theresa W. Depinet; J. Marie Haren; C. Lisa Kurtz; Nathaniel H. Robin; Suzanne B. Cassidy; Daynna J. Wolff; S. Schwartz (Human Genetics, 1998)

Clinical and genetic heterogeneity in Meckel syndrome - Paulina Paavola; Riitta Salonen; Alessandra Baumer; Albert Schinzel; P. A. Boyd; Steve Gould; H. Meusburger; Romano Tenconi; Angela Barnicoat; Robin Winter; L. Peltonen (Human Genetics, 1997)

Early Effects of CI-924 on hepatic peroxisome proliferation, microsomal enzyme induction, PCNA, and apoptosis in B6C3F1 mice and Wistar rats - A. H. Hofstra; Lena M. King; Robin M. Walker (Archives of Toxicology, 1997)

Sex ratios in bumble bee colonies: Complications due to orphaning? - Robin E. Owen; F. H. Rodd; R. C. Plowright (Behavioral Ecology and Sociobiology, 1980)